Toner for electrostatic image development

By using a composition of amorphous polyester resin A and crystalline polyester resin C, the problems of insufficient toner fixability and scratch resistance on polypropylene films in the prior art are solved, and efficient fixing is achieved. and scratch resistance.

CN113056707BActive Publication Date: 2025-01-14KAO CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN201980075703.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-11-20
Filing Date
2019-11-20
Publication Date
2025-01-14
Estimated Expiration
2039-11-20

AI Technical Summary

Technical Problem

The conventional electrostatic image developing toner is difficult to achieve fixability and scratch resistance on the polypropylene film, and the printed material is prone to peel off.

Method used

A composition of amorphous polyester resin A and crystalline polyester resin C is used. Resin A is formed by connecting polyester resin and modified polyolefin polymer A through covalent bonds. The modified polyolefin polymer The content of A is between 5% and 30%. This composition achieves excellent fixability to the polypropylene film and scratch resistance of the printed image.

Benefits of technology

It achieves efficient fixation of polypropylene film and scratch resistance of printed images, avoiding peeling off of printed materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003068761610000061
    Figure GDA0003068761610000061
  • Figure GDA0003068761610000411
    Figure GDA0003068761610000411
  • Figure GDA0003068761610000421
    Figure GDA0003068761610000421
Patent Text Reader

Abstract

The present invention relates to a toner for electrostatic image development having excellent fixability to polypropylene film and excellent scratch resistance of printed images, and a resin composition for toner for electrostatic image development, etc. A toner for electrostatic image development and a resin composition for toner for electrostatic image development, wherein the toner for electrostatic image development contains a non-crystalline polyester resin A and a crystalline polyester resin C, wherein the non-crystalline polyester resin A has a constituent part derived from a polyester resin and a constituent part derived from a modified polyolefin polymer A having a reactive functional group, wherein the constituent part derived from the polyester resin and the constituent part derived from the modified polyolefin polymer A are linked by a covalent bond, and the amount of the constituent part derived from the modified polyolefin polymer A is 5% by mass or more and 30% by mass or less relative to the total amount of resin components in the toner.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a toner and a resin composition for developing an electrostatic image, which are used for developing a latent image formed in an electrophotographic method, an electrostatic recording method, an electrostatic printing method, and the like. Background Art

[0002] In the field of electrophotography, as electrophotographic systems develop, development of toners for developing electrostatic images that are compatible with higher image quality and higher speed printing is sought.

[0003] Japanese Patent Application Laid-Open No. 2005-316378 (Patent Document 1) describes a compatibilizer and a polyester resin composition for toner, wherein the compatibilizer is characterized in that it is a compatibilizer for compatibilizing polyester and wax in a toner containing a binder resin containing at least polyester and wax, and is formed by reacting polyester with a maleic anhydride-modified polyolefin, and the polyester resin composition for toner contains a compatibilizer. It is described that the compatibilizer can improve the dispersibility of the wax in the toner, and produce a toner having excellent low-temperature fixing property, high-temperature offset resistance, anti-blocking property, wear resistance, and filming resistance.

[0004] Japanese Patent Application Laid-Open No. 2007-199300 (Patent Document 2) describes a toner for electrostatic image development, which is characterized by containing at least a crystalline polyester resin, a non-crystalline resin, and a copolymer of α-olefin and maleic anhydride. The toner has excellent color reproducibility and transparency.

[0005] Japanese Patent Application Laid-Open No. 2016-218448 (Patent Document 3) describes a binder resin composition for electrostatic image developing toner, which contains a polyester resin and a polypropylene wax (W-1), and the heat absorption ratio ΔH represented by the following formula (1) is: CW / W It is 0.10 or more and 0.80 or less.

[0006] Heat absorption ratio ΔH CW / W =ΔH CW / ΔH W (1)

[0007] ΔH CW : The endothermic value of the melting endothermic peak per 1 g of the polypropylene wax (W-1) when measured in the form of the above-mentioned adhesive resin composition

[0008] ΔH W : The endothermic value of the melting endothermic peak of the polypropylene wax (W-1) per 1 g when the polypropylene wax (W-1) is measured alone

[0009] It is described that the binder resin composition can provide a toner having excellent fixability to a PP (polypropylene) film. Summary of the invention

[0010] One embodiment of the present invention relates to the following [1] and [2].

[0011] [1] A toner for electrostatic image development, comprising an amorphous polyester resin A and a crystalline polyester resin C,

[0012] The amorphous polyester resin A comprises a constituent part derived from the polyester resin and a constituent part derived from the modified polyolefin polymer A having a reactive functional group, wherein the constituent part derived from the polyester resin and the constituent part derived from the modified polyolefin polymer A are connected by a covalent bond.

[0013] The amount of the structural part derived from the modified polyolefin polymer A is 5% by mass or more and 30% by mass or less based on the total amount of the resin components in the toner.

[0014] [2] A resin composition for electrostatic image developing toner, comprising an amorphous polyester resin A and a crystalline polyester resin C,

[0015] The amorphous polyester resin A comprises a constituent part derived from the polyester resin and a constituent part derived from the modified polyolefin polymer A having a reactive functional group, wherein the constituent part derived from the polyester resin and the constituent part derived from the modified polyolefin polymer A are connected by a covalent bond.

[0016] The amount of the structural part derived from the modified polyolefin polymer A is 5% by mass or more and 30% by mass or less based on the total amount of the resin components in the toner. DETAILED DESCRIPTION

[0017] As printing media become more diverse, there is a demand for electrophotographic printing on printing media other than paper. One of the main media is polypropylene film (hereinafter referred to as "PP film"), which is used for plastic bottle labels, various packages, etc. On the other hand, paper and polypropylene have very different characteristics as printing media, such as the polarity and surface state of the materials. Therefore, for example, the toners developed in the past described in Patent Documents 1 or 2 have the problem of not being fixed to the PP film.

[0018] Furthermore, even the toner disclosed in Patent Document 3 is expected to have better fixability to PP film. Furthermore, in view of the usage of labels on plastic bottles, etc., after printing on PP film, a toner is required that can produce an image with excellent scratch resistance without peeling off even if the printed matter is rubbed.

[0019] One embodiment of the present invention relates to a toner for electrostatic image development and a resin composition for electrostatic image development toner, which are excellent in fixing property to a polypropylene film and excellent in scratch resistance of a printed image.

[0020] According to one embodiment of the present invention, it is possible to provide a toner for electrostatic image development and a resin composition for electrostatic image development toner, which are excellent in fixing property to a polypropylene film and excellent in scratch resistance of a printed image.

[0021] [Toner for electrostatic image development]

[0022] An electrostatic image developing toner (hereinafter, also simply referred to as "toner") according to one embodiment of the present invention contains an amorphous polyester resin A (hereinafter, also simply referred to as "resin A") and a crystalline polyester resin C (hereinafter, also simply referred to as "resin C").

[0023] Resin A has a constituent part derived from a polyester resin and a constituent part derived from a modified polyolefin polymer A (hereinafter also referred to as "polymer A") having a reactive functional group, and the constituent part derived from the polyester resin and the constituent part derived from the modified polyolefin polymer A are connected by a covalent bond.

[0024] Furthermore, the amount of the constituent part derived from the polymer A is 5% by mass or more and 30% by mass or less based on the total amount of the resin components in the toner.

[0025] The above configuration can provide a toner having excellent fixability to polypropylene film and excellent scratch resistance of printed images. The reason for this is not clear, but it is considered as follows.

[0026] A toner according to one embodiment of the present invention contains an amorphous polyester resin A having a constituent part derived from a polyester resin and a constituent part derived from a polymer A. In the resin A, the constituent part derived from the polymer A and the constituent part derived from the polyester resin are linked by covalent bonds and have a structure in which they are composited at a molecular level. It is thought that in this case, the constituent part derived from the polymer A of the polyester resin A is oriented toward the PP film by fixing heating during printing on the PP film by an electrophotographic method, and an intermolecular interaction is exhibited between the PP film and the polyester resin A, thereby achieving excellent fixing properties to the PP film.

[0027] In contrast, it was found that by further containing a crystalline polyester resin C in the toner containing the resin A, the fixability to the film was improved, and the fixing strength was increased, thereby improving the peel strength and the scratch resistance. This is considered to be because the highly hydrophobic resin C has a high affinity for the constituent parts derived from the polymer A in the resin A and the PP film, and a strong intermolecular interaction occurs at the interface between them, or a strong bonding force is generated between the three components.

[0028] The definitions and the like of various terms in this specification are shown below.

[0029] Whether the resin is crystalline or amorphous is determined by the crystallinity index. The crystallinity index is defined by the ratio of the softening point of the resin in the measurement method described in the embodiments described later to the maximum peak temperature of the endothermic absorption originating from the resin or from the constituent part of the polyester resin (softening point (°C) / maximum peak temperature of the endothermic absorption (°C)). A crystalline resin refers to a resin having a crystallinity index of 0.65 or more and less than 1.4, preferably 0.7 or more, more preferably 0.9 or more, and preferably less than 1.2. An amorphous resin refers to a resin having a crystallinity index of 1.4 or more or less than 0.65. The crystallinity index can be appropriately adjusted according to the type and ratio of the raw monomers and the manufacturing conditions such as the reaction temperature, reaction time, and cooling rate. The endothermic peak originating from the constituent part of the polyester resin can be attributed by conventional methods, but usually appears closer to the low temperature side than the endothermic peak originating from the constituent part of polymer A. When it is unclear to which peak the peak should be attributed, the polyester resin alone and the polymer A alone were measured under the above conditions using a differential scanning calorimeter, and the endothermic peak with a temperature closer to each endothermic peak was attributed to the endothermic peak derived from each constituent part.

[0030] The term “carboxylic acid compound” is a concept that includes not only the carboxylic acid but also an acid anhydride that decomposes during a reaction to generate an acid and an alkyl ester of the carboxylic acid (for example, the alkyl group has 1 to 3 carbon atoms).

[0031] In the case where the carboxylic acid compound is an alkyl ester of carboxylic acid, the number of carbon atoms of the alkyl group which is the alcohol residue of the ester is not included in the number of carbon atoms of the carboxylic acid compound.

[0032] The “resin component” refers to the resin component contained in the toner including the amorphous polyester resin A, the amorphous polyester resin B, and the crystalline polyester resin C.

[0033] The toner contains resin A and resin C. The toner preferably further contains a non-crystalline polyester resin B having a softening point different from the softening point of resin A by 5° C. or more. The resin composition for electrostatic image developing toner also contains resin A and resin C, and preferably further contains a non-crystalline polyester resin B having a softening point different from the softening point of resin A by 5° C. or more.

[0034] In the toner, from the viewpoint of obtaining a toner having excellent fixability to PP film and excellent scratch resistance of a printed image, the amount of constituent parts derived from polymer A in resin A is 5% by mass or more and 30% by mass or less relative to the total amount of resin components in the toner.

[0035] From the viewpoint of improving the fixability to the PP film, the amount of the constituent parts derived from the polymer A is preferably 8% by mass or more, more preferably 9% by mass or more, and further preferably 10% by mass or more, and is preferably 25% by mass or less, and more preferably 20% by mass or less, relative to the total amount of the resin components in the toner.

[0036] The amount of the constituent part derived from the polymer A is calculated according to the following formula.

[0037] Amount of constituents derived from polymer A (mass %) = {[amount of resin containing constituents derived from polymer A × ratio of constituents derived from polymer A in the resin] / [total amount of resin components in toner]} × 100

[0038] Furthermore, the toner contains, for example, toner particles and external additives.

[0039] <Toner particles>

[0040] The toner particles preferably contain resin A and resin C, and more preferably contain resin A, resin B, and resin C.

[0041] In addition, the toner particles may contain additives such as colorants, waxes, charge control agents, magnetic powders, flow improvers, conductivity regulators, reinforcing fillers such as fibrous substances, antioxidants, anti-aging agents, and cleanliness improvers.

[0042] [Amorphous polyester resin A]

[0043] From the viewpoint of obtaining a toner having excellent fixability to PP film and excellent scratch resistance of a printed image, the amorphous polyester resin A has a constituent part derived from the polyester resin and a constituent part derived from the modified polyolefin polymer A having a reactive functional group, and the constituent part derived from the polyester resin and the constituent part derived from the modified polyolefin polymer A are connected by a covalent bond.

[0044] The polyester resin A may be a polyester resin modified to such an extent that its properties are not substantially impaired. Examples of the modified polyester resin include urethane-modified polyester resins in which a constituent part derived from the polyester resin is modified with a urethane bond, and epoxy-modified polyester resins in which a constituent part derived from the polyester resin is modified with an epoxy bond.

[0045] Linked by covalent bonds means that the constituent parts are linked by covalent bonds.

[0046] Examples of constituent parts linked by covalent bonds include ester bonds, ether bonds, amide bonds, urethane bonds, and bonds having these bonds and a linking group.

[0047] Examples of the linking group include divalent or higher-valent hydrocarbon groups having a carbon number of 1 to 6. Examples of the linking group include a methylene group, an ethylene group, a propylene group, and a phenylene group.

[0048] Among them, connection via an ester bond is preferred, and direct connection via an ester bond is more preferred.

[0049] (Derived from the constituent parts of polyester resin)

[0050] Hereinafter, the constituent parts derived from the polyester resin will be described.

[0051] The "constituent part derived from the polyester resin" refers to a constituent part of the resin in which a part of the polyester resin is bonded to another molecular group.

[0052] The polyester resin is, for example, a polycondensate of an alcohol component and a carboxylic acid component.

[0053] (Alcohol component)

[0054] The alcohol component includes, for example, divalent or higher alcohols.

[0055] The content of the divalent or higher alcohol is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and is 100% by mass or less.

[0056] Examples of the divalent or higher alcohol include diols having an aromatic group, linear or branched aliphatic diols, alicyclic diols, and trivalent or higher polyols. Among them, diols having an aromatic group or linear or branched aliphatic diols are preferred, diols having an aromatic group are more preferred, and alkylene oxide adducts of aromatic diols are further preferred.

[0057] The alkylene oxide adduct of an aromatic diol is preferably an alkylene oxide adduct of bisphenol A, and more preferably an alkylene oxide adduct of bisphenol A represented by formula (I):

[0058] [Chemical formula 1]

[0059]

[0060] (In the formula, OR 1 and R 2 O is oxyalkylene, R 1 and R 2Each is independently an ethylene group or a propylene group, x and y represent the average number of added moles of alkylene oxide, each is a positive number, and the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, and more preferably 4 or less).

[0061] Examples of the alkylene oxide adduct of bisphenol A include propylene oxide adduct of bisphenol A and ethylene oxide adduct of bisphenol A. One or more of these may be used. Among them, propylene oxide adduct of bisphenol A is preferred from the viewpoint of further improving the fixability to the PP film.

[0062] From the viewpoint of further improving scratch resistance, the amount of the alkylene oxide adduct of bisphenol A in the alcohol component is preferably 70 mol% or more, more preferably 90 mol% or more, further preferably 95 mol% or more, and is 100 mol% or less, further preferably 100 mol%.

[0063] As the linear or branched aliphatic diol, an aliphatic diol having a hydroxyl group bonded to a secondary carbon atom is preferred. The number of carbon atoms in the aliphatic diol having a hydroxyl group bonded to a secondary carbon atom is preferably 3 or more and 4 or less. Examples of the aliphatic diol having a hydroxyl group bonded to a secondary carbon atom include 1,2-propylene glycol, 1,2-butanediol, 1,3-butanediol, and 2,3-butanediol.

[0064] When the alcohol component contains an aliphatic diol having a hydroxyl group bonded to a secondary carbon atom, the amount of the aliphatic diol having a hydroxyl group bonded to a secondary carbon atom is preferably 70 mol% or more, more preferably 90 mol% or more, further preferably 95 mol% or more in the alcohol component, and is 100 mol% or less, further preferably 100 mol%.

[0065] Examples of other linear or branched aliphatic diols include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol.

[0066] Examples of the alicyclic diol include hydrogenated bisphenol A [2,2-bis(4-hydroxycyclohexyl)propane] and alkylene oxide (average addition mole number of 2 to 12) adducts of hydrogenated bisphenol A having 2 to 4 carbon atoms.

[0067] Examples of the trivalent or higher polyol include glycerin, pentaerythritol, trimethylolpropane, and sorbitol.

[0068] These alcohol components may be used alone or in combination of two or more.

[0069] (Carboxylic acid component)

[0070] The carboxylic acid component includes, for example, a divalent or higher-valent carboxylic acid compound.

[0071] The content of the divalent or higher carboxylic acid compound is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and is 100% by mass or less.

[0072] Examples of the divalent or higher carboxylic acid compound include aromatic dicarboxylic acid compounds, linear or branched aliphatic dicarboxylic acid compounds, alicyclic dicarboxylic acid compounds, and trivalent or higher polycarboxylic acid compounds. Among them, aromatic dicarboxylic acid compounds are preferred.

[0073] Examples of the aromatic dicarboxylic acid include phthalic acid, isophthalic acid, and terephthalic acid. Among them, isophthalic acid and terephthalic acid are preferred, and terephthalic acid is more preferred.

[0074] The amount of the aromatic dicarboxylic acid in the carboxylic acid component is preferably 30 mol% or more, more preferably 50 mol% or more, further preferably 80 mol% or more, further preferably 90 mol% or more, and is 100 mol% or less.

[0075] The number of carbon atoms of the linear or branched aliphatic dicarboxylic acid is preferably 2 or more, more preferably 4 or more, further preferably 8 or more, further preferably 10 or more, and is preferably 22 or less, more preferably 16 or less.

[0076] Examples of the linear or branched aliphatic dicarboxylic acid include oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, sebacic acid, dodecanedioic acid, tetradecanedioic acid, succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms, or anhydrides or alkyl esters having 1 to 3 carbon atoms thereof.

[0077] Examples of the succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms include dodecyl succinic acid, dodecenyl succinic acid, and octenyl succinic acid. Among them, succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms, or anhydrides thereof are preferred.

[0078] When the carboxylic acid component contains a linear or branched aliphatic dicarboxylic acid, the amount of the linear or branched aliphatic dicarboxylic acid in the carboxylic acid component is preferably 2 mol% or more, more preferably 3 mol% or more, further preferably 5 mol% or more, and is preferably 30 mol% or less, more preferably 20 mol% or less, further preferably 10 mol% or less.

[0079] As the trivalent or higher polycarboxylic acid, a trivalent carboxylic acid is preferred, and examples thereof include trimellitic acid or its anhydride. Among them, trimellitic acid or its anhydride is preferred.

[0080] When the carboxylic acid component contains a trivalent or higher polycarboxylic acid, the amount of the trivalent or higher polycarboxylic acid in the carboxylic acid component is preferably 1 mol% or more, more preferably 5 mol% or more, further preferably 10 mol% or more, and is preferably 35 mol% or less, more preferably 30 mol% or less.

[0081] These carboxylic acid components may be used alone or in combination of two or more.

[0082] The equivalent ratio of the carboxyl group of the carboxylic acid component to the hydroxyl group of the alcohol component (COOH group / OH group) is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.

[0083] (Derived from the constituent part of polymer A)

[0084] The resin A has a constituent part derived from the polymer A from the viewpoint of obtaining a toner having excellent fixability to a PP film and excellent scratch resistance of a printed image.

[0085] The "constituent part derived from polymer A" refers to a constituent part of resin A in which a part of polymer A is bonded to another molecular group.

[0086] The polymer A is a modified polyolefin polymer A from the viewpoint of improving the fixability to the PP film and the scratch resistance of the printed image.

[0087] Examples of the modified polyolefin-based polymer A include modified polyethylene-based polymers, modified polypropylene-based polymers, and modified polybutene-based polymers.

[0088] Among them, modified polypropylene-based polymers are preferred from the viewpoint of further improving the fixability to the PP film and the scratch resistance of the printed image.

[0089] The modified polyolefin polymer A has a reactive functional group, and examples of the reactive functional group include a carboxylic acid group, a carboxylic acid anhydride group, and a hydroxyl group. Among them, a carboxylic acid group or a carboxylic acid anhydride group is preferred.

[0090] From the viewpoint of improving fixability to PP film and scratch resistance of printed images, polymer A is a polypropylene polymer modified with a carboxylic acid compound having an unsaturated bond or its anhydride (hereinafter also referred to as "acid-modified polypropylene polymer").

[0091] Examples of the polypropylene-based polymer before modification include polypropylene and copolymers of propylene and other olefins.

[0092] Examples of the polypropylene include polypropylene obtained by a method of obtaining by general polymerization of propylene, a method of obtaining by thermally decomposing polypropylene used in general molding containers, and a method of separating and purifying a low-molecular-weight polypropylene generated as a by-product when producing polypropylene used in general molding containers.

[0093] Examples of the copolymer of propylene and other olefins include copolymers obtained by polymerizing propylene and other olefins having an unsaturated bond copolymerizable with propylene. The copolymer may be any of a random copolymer and a block copolymer.

[0094] Examples of other olefins include ethylene and olefins having a carbon number of 4 to 10. Examples of other olefins include ethylene, butene, pentene, hexene, and 2-ethylhexene.

[0095] Examples of copolymers of propylene and other olefins include propylene / hexene copolymers and ethylene / propylene copolymers.

[0096] Among these polypropylene-based polymers before modification, polypropylene is preferred from the viewpoint of improving the fixability to the PP film and the scratch resistance of the printed image.

[0097] Examples of the acid-modified polypropylene polymer include a polypropylene polymer terminally modified with a carboxylic acid compound having an unsaturated bond or its anhydride (hereinafter, also referred to as “terminal-modified polypropylene polymer”), and a polypropylene polymer randomly graft-modified with a carboxylic acid compound having an unsaturated bond or its anhydride (hereinafter, also referred to as “random graft-modified polypropylene polymer”).

[0098] Among them, from the viewpoint of improving the fixability to the PP film and the scratch resistance of the printed image, a polypropylene polymer terminally modified with a carboxylic acid compound having an unsaturated bond or its anhydride is preferred. The terminal-modified polypropylene polymer is preferably a polypropylene polymer in which only one terminal is modified with a carboxylic acid compound having an unsaturated bond or its anhydride (hereinafter also referred to as "single-terminal modified polypropylene polymer").

[0099] Examples of the carboxylic acid compound having an unsaturated bond or an anhydride thereof include maleic anhydride, fumaric acid, and itaconic acid. Among them, maleic anhydride is preferred.

[0100] As a polypropylene polymer terminally modified with a carboxylic acid compound or an anhydride thereof having an unsaturated bond, for example, it can be obtained by subjecting a polypropylene polymer terminally modified with a carboxylic acid compound or an anhydride thereof having an unsaturated bond to an ene reaction. A polypropylene polymer terminally modified with an unsaturated bond can be obtained by a known method, and can be produced using, for example, a vanadium catalyst, a titanium catalyst, a zirconium catalyst, etc.

[0101] Examples of the polymer A include terminal maleic anhydride-modified polypropylene and copolymers of terminal maleic anhydride-modified propylene and other olefins.

[0102] Among them, from the viewpoint of improving the fixability to polypropylene film, terminal maleic anhydride modified polypropylene is preferred, and single-terminal maleic anhydride modified polypropylene is more preferred. By introducing maleic anhydride sites into polypropylene polymers, two constituent sites from polyester resins can be connected by ester bonds. In particular, it can be considered that by using single-terminal maleic anhydride modified polypropylene polymers, a polyester resin having a structure obtained by connecting two constituent sites from polyester resins using maleic anhydride sites at the ends of polypropylene polymers can be obtained. Therefore, it can be considered that by using single-terminal maleic anhydride modified polypropylene polymers, the fixability to polypropylene film can be further improved.

[0103] Examples of commercially available terminal-modified polypropylene polymers include single-terminal maleic anhydride-modified polypropylene "X-10065" (Mn=1000), single-terminal maleic anhydride-modified polypropylene "X-10088" (Mn=2500), single-terminal maleic anhydride-modified polypropylene "X-10082" (Mn=8000), single-terminal maleic anhydride-modified propylene / hexene copolymer "X-10087" (Mn=800), single-terminal maleic anhydride-modified propylene / hexene copolymer "X-10053" (Mn=2000), and single-terminal maleic anhydride-modified propylene / hexene copolymer "X-10052" (Mn=4000) (all manufactured by BAKER HUGHES).

[0104] The randomly graft-modified polypropylene polymer is preferably a polypropylene polymer modified by randomly grafting maleic anhydride (hereinafter also referred to as a "randomly grafted maleic anhydride-modified polypropylene polymer").

[0105] The random grafted maleic anhydride-modified polypropylene polymer is preferably modified by grafting one or more maleic anhydride in one molecule. Whether it is modified by maleic anhydride can be determined by a common spectrum measurement. If it is modified by maleic anhydride, the double bond of maleic anhydride becomes a single bond, so it can be determined by the change in its spectrum.

[0106] The random graft-modified polypropylene-based polymer can be obtained, for example, by generating free radicals in the polypropylene-based polymer molecule and reacting the free radicals with a carboxylic acid compound having an unsaturated bond or an anhydride thereof.

[0107] As commercially available products of the randomly grafted modified polypropylene-based polymers, for example, there can be mentioned “M-100”, “M-300”, “M-310”, “PMA H1000A”, “PMA H1100A”, “PMA H3000A”, “PMA-T”, “PMA-F2”, and “PMA-L” of the “TOYO-TAC” series (all manufactured by Toyobo Co., Ltd.); “1001”, “1010”, “100TS”, and “110TS” of the “Youmex” series (all manufactured by Sanyo Chemical Industries, Ltd.); and “003” and “006” of the “KAYABRITE” series (all manufactured by Akzo Nobel Co., Ltd.).

[0108] From the viewpoint of further improving the fixability to the PP film, the melting point of the polymer A is preferably 10° C. or higher, more preferably 20° C. or higher, more preferably 40° C. or higher, more preferably 60° C. or higher, more preferably 70° C. or higher, more preferably 80° C. or higher, and is preferably 170° C. or lower, more preferably 150° C. or lower, more preferably 140° C. or lower, more preferably 120° C. or lower, and more preferably 100° C. or lower.

[0109] From the viewpoint of further improving the fixability to the PP film, the acid value of the polymer A is preferably 200 mgKOH / g or less, more preferably 150 mgKOH / g or less, further preferably 100 mgKOH / g or less, and is preferably 0.1 mgKOH / g or more, more preferably 1 mgKOH / g or more, further preferably 5 mgKOH / g or more, further preferably 10 mgKOH / g or more.

[0110] The melting point and the acid value were measured according to the method described in the Examples.

[0111] From the viewpoint of further improving the fixability to the PP film, the number average molecular weight of the polymer A is preferably 300 or more, more preferably 500 or more, more preferably 700 or more, and more preferably 800 or more, and is preferably 50,000 or less, more preferably 15,000 or less, more preferably 8,000 or less, more preferably 4,000 or less, and further preferably 3,000 or less.

[0112] The number average molecular weight is measured by gel permeation chromatography using polystyrene as a standard sample.

[0113] In the amorphous polyester resin A, from the viewpoint of improving the fixability and scratch resistance to the PP film, the amount of the constituent parts derived from the polymer A is preferably 5% by mass or more, more preferably 8% by mass or more, further preferably 10% by mass or more, further preferably 15% by mass or more, and from the viewpoint of improving the storage stability, it is preferably 80% by mass or less, more preferably 60% by mass or less, further preferably 40% by mass or less, further preferably 35% by mass or less.

[0114] Among the above amounts, the amount of the polyester resin A is the total amount of the polymer A and the raw material monomers, and is the amount after excluding the amount of dehydration due to polycondensation.

[0115] [Method for producing resin A]

[0116] Resin A can be obtained, for example, by the following method:

[0117] (a) a method comprising polycondensing raw material monomers containing an alcohol component and a carboxylic acid component in the presence of a modified polyolefin polymer A having a reactive functional group; or

[0118] (b) A method comprising reacting a modified polyolefin polymer A having a reactive functional group with a polyester resin.

[0119] The reaction (b) may be, for example, dehydration condensation or transesterification when the reactive functional group is a carboxylic acid group or a carboxylic acid anhydride group. The reaction conditions are preferably conditions under which the carboxylic acid group or carboxylic acid anhydride group of the polymer A undergoes dehydration condensation or transesterification with an alcohol component, a carboxylic acid component, or the like.

[0120] The polycondensation of the alcohol component and the carboxylic acid component can be carried out, for example, in an inert gas atmosphere in the presence of an esterification catalyst, an inhibitor, etc., as required, at a temperature of about 150°C or more and about 250°C or less. As the esterification catalyst, for example, tin compounds such as dibutyltin oxide, 2-ethylhexanoate tin (II), and titanium compounds such as di(triethanolamine) titanate diisopropyl can be cited. As an esterification cocatalyst that can be used together with the esterification catalyst, for example, gallic acid can be cited. The amount of the esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 1 part by mass or less, and more preferably 0.8 parts by mass or less, relative to 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. The amount of the esterification cocatalyst used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, and more preferably 0.1 parts by mass or less.

[0121] [Physical properties of resin A]

[0122] From the viewpoint of further improving scratch resistance, the softening point of resin A is preferably 80° C. or higher, more preferably 90° C. or higher, and further preferably 100° C. or higher. From the viewpoint of further improving fixability to PP film, it is preferably 170° C. or lower, more preferably 150° C. or lower, further preferably 120° C. or lower, and further preferably 110° C. or lower.

[0123] From the viewpoint of further improving storage stability, the glass transition temperature of resin A is preferably 40° C. or higher, more preferably 50° C. or higher, and from the viewpoint of further improving fixability to PP film, it is preferably 80° C. or lower, more preferably 70° C. or lower, and even more preferably 60° C. or lower.

[0124] From the viewpoint of further improving the fixability to the PP film, the crystalline melting peak of the resin A originating from the constituent part of the polymer A is preferably not observed, or is 140°C or lower, more preferably 130°C or lower, further preferably 120°C or lower, further preferably 110°C or lower, and is preferably 60°C or higher, more preferably 70°C or higher, further preferably 80°C or higher.

[0125] The method for measuring the crystal melting peak temperature derived from the polymer A is based on the method described in Examples.

[0126] The amount of resin A relative to the total amount of resin components in the colorant is preferably 20 mass % or more, more preferably 30 mass % or more, further preferably 40 mass % or more, and is preferably 90 mass % or less, more preferably 80 mass % or less, further preferably 70 mass % or less, further preferably 60 mass % or less.

[0127] [Amorphous polyester resin B]

[0128] The toner may contain a non-crystalline polyester resin B (hereinafter, also simply referred to as “resin B”) having a softening point different from that of the resin A by 5° C. or more.

[0129] The softening point of resin B is preferably higher than that of resin A. Resin B more preferably has a softening point that is 10°C or higher than that of resin A, further preferably has a softening point that is 15°C or higher than that of resin A, and further preferably has a softening point that is 20°C or higher than that of resin A.

[0130] Resin B is a polycondensate of an alcohol component and a carboxylic acid component. The alcohol component and the carboxylic acid component are as exemplified in the above-mentioned resin A.

[0131] [Physical properties of resin B]

[0132] From the viewpoint of further improving the storage stability, the softening point of the resin B is preferably 90°C or higher, more preferably 110°C or higher, further preferably 120°C or higher, and is preferably 170°C or lower, more preferably 150°C or lower, further preferably 140°C or lower, further preferably 130°C or lower.

[0133] The glass transition temperature of the resin B is preferably 50° C. or higher, more preferably 55° C. or higher, and further preferably 60° C. or higher, and is preferably 80° C. or lower, more preferably 75° C. or lower, and further preferably 70° C. or lower.

[0134] The softening point and glass transition temperature of resin B can be appropriately adjusted according to the types and amounts of raw material monomers used and production conditions such as reaction temperature, reaction time, and cooling rate. In addition, these values ​​can be obtained by the methods described in Examples.

[0135] Resin B is obtained, for example, by polycondensation of an alcohol component and a carboxylic acid component. The conditions for the polycondensation, for example, the reaction conditions described in the method for producing resin A can be applied.

[0136] When resin B is contained, the mass ratio of resin A to resin B [resin A / resin B] is preferably 20 / 80 or more, more preferably 30 / 70 or more, further preferably 40 / 60 or more, and is preferably 90 / 10 or less, more preferably 70 / 30 or less, further preferably 60 / 40 or less.

[0137] When resin B is contained, the content of resin B in the resin component of the colorant is preferably 10 mass % or more, more preferably 20 mass % or more, further preferably 30 mass % or more, and is preferably 80 mass % or less, more preferably 70 mass % or less, further preferably 60 mass % or less, further preferably 50 mass % or less.

[0138] When resin B is contained, the total amount of resin A and resin B is preferably 40 mass % or more, more preferably 60 mass % or more, further preferably 65 mass % or more, further preferably 70 mass % or more, further preferably 80 mass % or more, further preferably 90 mass % or more, and is preferably 99.9 mass % or less, more preferably 99 mass % or less, further preferably 97 mass % or less, relative to the total amount of resin components in the colorant.

[0139] [Crystalline polyester resin C]

[0140] The toner contains a crystalline polyester resin C (hereinafter, also simply referred to as “resin C”).

[0141] Resin C preferably has at least a polyester resin segment formed by a polycondensate of an alcohol component including an α,ω-aliphatic diol and a carboxylic acid component including an aliphatic dicarboxylic acid, and more preferably has the polyester resin segment and an addition polymerization-based resin segment of an addition polymer of a raw material monomer including a styrene-based compound.

[0142] (Alcohol component)

[0143] The alcohol component contains α,ω-aliphatic diol.

[0144] The α,ω-aliphatic diol is preferably an α,ω-straight-chain aliphatic diol.

[0145] The number of carbon atoms in the α,ω-aliphatic diol is preferably 2 or more, more preferably 4 or more, further preferably 6 or more, further preferably 8 or more, further preferably 10 or more, and is preferably 16 or less, more preferably 14 or less, further preferably 12 or less.

[0146] Examples of the α,ω-aliphatic diol include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, and 1,14-tetradecanediol. Among them, ethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,10-decanediol, or 1,12-dodecanediol is preferred, and 1,10-decanediol or 1,12-dodecanediol is more preferred.

[0147] The amount of the α,ω-aliphatic diol in the alcohol component is preferably 80 mol% or more, more preferably 85 mol% or more, further preferably 90 mol% or more, further preferably 95 mol% or more, and is 100 mol% or less, further preferably 100 mol%.

[0148] The alcohol component may contain other alcohol components other than α,ω-aliphatic diol. Examples of other alcohol components include aliphatic diols other than α,ω-aliphatic diols such as 1,2-propylene glycol and neopentyl glycol; aromatic diols such as alkylene oxide adducts of bisphenol A; trivalent diols such as glycerol, pentaerythritol, and trimethylolpropane;

[0149] The above alcohols, etc. These alcohol components can be used alone or in combination of two or more.

[0150] (Carboxylic acid component)

[0151] The carboxylic acid component contains an aliphatic dicarboxylic acid.

[0152] The aliphatic dicarboxylic acid is preferably a straight-chain aliphatic dicarboxylic acid.

[0153] The carbon number of the aliphatic dicarboxylic acid is preferably 4 or more, more preferably 8 or more, further preferably 10 or more, and is preferably 14 or less, more preferably 12 or less.

[0154] Examples of the aliphatic dicarboxylic acid include fumaric acid, sebacic acid, dodecanedioic acid, and tetradecanedioic acid. Among them, sebacic acid or dodecanedioic acid is preferred, and sebacic acid is more preferred. One or more of these carboxylic acid components may be used.

[0155] The amount of the aliphatic dicarboxylic acid in the carboxylic acid component is preferably 80 mol% or more, more preferably 85 mol% or more, further preferably 90 mol% or more, further preferably 95 mol% or more, and is 100 mol% or less, further preferably 100 mol%.

[0156] The carboxylic acid component may contain other carboxylic acid components different from the aliphatic dicarboxylic acid. Examples of other carboxylic acid components include aromatic dicarboxylic acids such as terephthalic acid and isophthalic acid; and trivalent or higher polycarboxylic acids. These carboxylic acid components may be used alone or in combination of two or more.

[0157] The equivalent ratio of the carboxyl group of the carboxylic acid component to the hydroxyl group of the alcohol component (COOH group / OH group) is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.

[0158] (Addition polymerization resin segment)

[0159] The addition polymerization-based resin segment is, for example, an addition polymer of a raw material monomer including a styrene-based compound.

[0160] Examples of the styrene-based compound include substituted or unsubstituted styrenes, and examples of the substituent include an alkyl group having 1 to 5 carbon atoms, a halogen atom, an alkoxy group having 1 to 5 carbon atoms, a sulfonic acid group or a salt thereof.

[0161] Examples of the styrene-based compound include styrene, methylstyrene, α-methylstyrene, β-methylstyrene, tert-butylstyrene, chlorostyrene, chloromethylstyrene, methoxystyrene, styrenesulfonic acid or salts thereof, and the like. Among them, styrene is preferred.

[0162] The content of the styrene-based compound in the raw material monomers of the addition polymerization-based resin segment is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 90% by mass or more, and is 100% by mass or less, preferably 98% by mass or less, and more preferably 95% by mass or less.

[0163] As other raw material monomers, for example, there can be mentioned alkyl esters of (meth)acrylic acid such as 2-ethylhexyl (meth)acrylate; ethylenically unsaturated monoolefins such as ethylene and propylene; conjugated dienes such as butadiene; halogenated vinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; aminoalkyl (meth)acrylates such as dimethylaminoethyl (meth)acrylate; vinyl ethers such as methyl vinyl ether; vinylidene halides such as vinylidene chloride; and N-vinyl compounds such as N-vinyl pyrrolidone.

[0164] (Structural unit derived from direactive monomers)

[0165] In order to connect the polyester resin segment and the addition polymerization resin segment, the resin C preferably has a structural unit derived from a bireactive monomer that is bonded to the polyester resin segment and the addition polymerization resin segment by a covalent bond.

[0166] The "structural unit derived from a direactive monomer" refers to a unit in which a functional group or an ethylenically unsaturated group of a direactive monomer has reacted.

[0167] As the bireactive monomer, for example, there can be mentioned an ethylenically unsaturated monomer having at least one functional group selected from a hydroxyl group, a carboxyl group, an epoxy group, a primary amino group and a secondary amino group in the molecule. Among them, from the viewpoint of reactivity, an ethylenically unsaturated monomer having a hydroxyl group or a carboxyl group is preferred, and an ethylenically unsaturated monomer having a carboxyl group is more preferred.

[0168] Examples of the dual-reactive monomer include acrylic acid, methacrylic acid, fumaric acid, maleic acid, etc. Among them, acrylic acid and methacrylic acid are preferred, and acrylic acid is more preferred from the viewpoint of reactivity in both polycondensation reaction and addition polymerization reaction.

[0169] The amount of the structural unit derived from the amphireactive monomer is preferably 1 mol part or more, more preferably 3 mol parts or more, and further preferably 5 mol parts or more, relative to 100 mol parts of the alcohol component of the polyester resin segment of the resin C, and is preferably 30 mol parts or less, more preferably 25 mol parts or less, and further preferably 20 mol parts or less.

[0170] The amount of the polyester resin segment in the resin C is preferably 40% by mass or more, more preferably 50% by mass or more, and is preferably 95% by mass or less, more preferably 85% by mass or less.

[0171] The amount of the addition polymerization resin segment in the resin C is preferably 5 mass % or more, more preferably 10 mass % or more, further preferably 15 mass % or more, and is preferably 60 mass % or less, more preferably 50 mass % or less.

[0172] The amount of the structural unit derived from the amphireactive monomer in the resin C is preferably 0.1 mass % or more, more preferably 0.5 mass % or more, further preferably 0.8 mass % or more, and is preferably 10 mass % or less, more preferably 5 mass % or less, further preferably 3 mass % or less.

[0173] When resin C has a polyester resin segment and an addition polymerization resin segment, the total amount of the polyester resin segment, the addition polymerization resin segment and the structural unit derived from the bireactive monomer is preferably 80 mass % or more, more preferably 90 mass % or more, further preferably 93 mass % or more, further preferably 95 mass % or more, and is 100 mass % or less.

[0174] The above amount is calculated based on the ratio of the raw material monomers of the polyester resin segment, the addition polymerization resin segment, the two reactive monomers, and the polymerization initiator, and does not include the dehydration amount caused by polycondensation in the polyester resin segment, etc. It should be noted that when a polymerization initiator is used, the mass of the polymerization initiator is included in the addition polymerization resin segment and calculated.

[0175] [Method for producing resin C]

[0176] The method for producing the resin C includes, for example, polycondensing an alcohol component and a carboxylic acid component, and addition polymerizing a raw material monomer of an addition polymerization-based resin segment and a bireactive monomer.

[0177] The conditions for polycondensation are as described in the method for producing the resin A, and if necessary, a radical polymerization inhibitor such as 4-tert-butylcatechol may be used in an amount of 0.001 to 0.5 parts by mass based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component.

[0178] From the viewpoint of further promoting polycondensation and, if necessary, reaction with a bireactive monomer, it is preferred that a portion of the carboxylic acid component is subjected to polycondensation, then addition polymerization is performed, the reaction temperature is raised again, and the remainder is added to the reaction system.

[0179] In addition polymerization, the raw material monomer of the addition polymerization resin segment and the bireactive monomer are subjected to addition polymerization. The temperature of the addition polymerization is preferably 110° C. or higher, more preferably 130° C. or higher, and preferably 220° C. or lower, more preferably 200° C. or lower. In addition, it is preferred to promote the reaction by reducing the pressure of the reaction system in the second half of the polymerization.

[0180] As the polymerization initiator for addition polymerization, for example, a known polymerization initiator may be used, such as a peroxide such as di-tert-butyl peroxide, a persulfate such as sodium persulfate, and an azo compound such as 2,2′-azobis(2,4-dimethylvaleronitrile).

[0181] The amount of the polymerization initiator used is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and further preferably 5 parts by mass or more, and is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and further preferably 10 parts by mass or less, relative to 100 parts by mass of the raw material monomers of the addition polymerization resin segment.

[0182] [Physical properties of resin C]

[0183] From the viewpoint of further improving scratch resistance, the softening point of resin C is preferably 60° C. or higher, more preferably 70° C. or higher, and further preferably 80° C. or higher. From the viewpoint of further improving fixability to PP film, it is preferably 170° C. or lower, more preferably 150° C. or lower, further preferably 120° C. or lower, and further preferably 110° C. or lower.

[0184] From the viewpoint of further improving scratch resistance, the melting point of resin C is preferably 50° C. or higher, more preferably 60° C. or higher, and further preferably 70° C. or higher. From the viewpoint of further improving fixability to PP film, it is preferably 100° C. or lower, more preferably 95° C. or lower, and further preferably 90° C. or lower.

[0185] From the viewpoint of further improving the fixability to the PP film and the scratch resistance of the printed image, the solubility parameter (hereinafter also referred to as “SP value”) of the resin C based on Fedors is preferably 9.0 (cal / cm 3 ) 1 / 2 More preferably, 9.2 (cal / cm 3 ) 1 / 2 More preferably, 9.4 (cal / cm 3 ) 1 / 2 More than 10.5 (cal / cm 3 ) 1 / 2 Below, more preferably 10.3 (cal / cm 3 ) 1 / 2 Below, more preferably 9.9 (cal / cm 3 ) 1 / 2 Below, more preferably 9.8 (cal / cm 3 ) 1 / 2 Below, more preferably 9.7 (cal / cm 3 ) 1 / 2 Below, more preferably 9.6 (cal / cm 3 ) 1 / 2 the following.

[0186] The "SP value" in this specification refers to a value calculated by the method described in [POLYMER ENGINEERING AND SCIENCE, FEBRUARY, 1974, Vol. 14, No. 2, ROBERT F. FEDORS. (pp. 147 to 154)] proposed by Fedors et al.

[0187] The softening point, glass transition temperature and SP value of resin C can be appropriately adjusted according to the type and amount of raw material monomers used, as well as production conditions such as reaction temperature, reaction time, cooling rate, etc. In addition, the values ​​of softening point and glass transition temperature can be obtained according to the method described in the examples.

[0188] The amount of resin C relative to the total amount of resin components in the colorant is preferably 0.1 mass % or more, more preferably 1 mass % or more, further preferably 3 mass % or more, and is preferably 60 mass % or less, more preferably 40 mass % or less, further preferably 35 mass % or less, further preferably 30 mass % or less, further preferably 20 mass % or less, further preferably 10 mass % or less.

[0189] The mass ratio of the amount of resin C to the total amount of resin A and resin B (resin C / (resin A+resin B)) is preferably 0.1 / 99.9 or more, more preferably 1 / 99 or more, further preferably 3 / 97 or more, and is preferably 60 / 40 or less, more preferably 40 / 60 or less, further preferably 35 / 65 or less, further preferably 30 / 70 or less.

[0190] The mass ratio of the amount of the constituent parts derived from the modified polyolefin polymer A to the amount of the crystalline polyester resin C (polymer A / resin C) is preferably 10 / 90 or more, more preferably 20 / 80 or more, further preferably 30 / 70 or more, further preferably 40 / 60 or more, and is preferably 90 / 10 or less, more preferably 80 / 20 or less, further preferably 75 / 25 or less.

[0191] [Colorant]

[0192] The toner may contain a colorant.

[0193] As the colorant, all dyes and pigments used as colorants for toners can be used, such as carbon black, phthalocyanine blue, permanent brown FG, fast brilliant scarlet, pigment green B, rhodamine-B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, magenta 6B, and disazo yellow. The toner may be any of a black toner and other color toners.

[0194] The content of the colorant is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and further preferably 3 parts by mass or more, relative to 100 parts by mass of the total amount of the resin component of the colorant, and is preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and further preferably 10 parts by mass or less.

[0195] [Release agent]

[0196] The toner may contain a releasing agent.

[0197] Examples of the release agent include wax.

[0198] Examples of the wax include polypropylene wax, polyethylene wax, polypropylene polyethylene copolymer wax; aliphatic hydrocarbon waxes such as microcrystalline wax, paraffin wax, Fischer-Tropsch wax, and Sasol wax, or oxides thereof; ester waxes such as carnauba wax, montan wax, or deacidified waxes thereof, and fatty acid ester waxes; fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts, etc. One or more of these can be used.

[0199] The melting point of the release agent is preferably 60° C. or higher, more preferably 70° C. or higher, and is preferably 160° C. or lower, more preferably 140° C. or lower, and further preferably 120° C. or lower.

[0200] The content of the release agent is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and further preferably 1.5 parts by mass or more, and is preferably 10 parts by mass or less, and more preferably 8 parts by mass or less, based on 100 parts by mass of the total amount of the resin components of the toner.

[0201] [Charge control agent]

[0202] The toner may contain a charge control agent.

[0203] The charge control agent may be a positively chargeable charge control agent or a negatively chargeable charge control agent.

[0204] Examples of the positively charged charge control agent include nigrosine dyes such as "Nigrosine base EX", "OilBlack BS", "Oil Black SO", "BONTRON N-01", "BONTRON N-04", "BONTRON N-07", "BONTRON N-09", and "BONTRON N-11" (all manufactured by Orient Chemical Industries, Ltd.); triphenylmethane dyes containing a tertiary amine as a side chain, and quaternary ammonium salt compounds such as "BONTRON p-51" (manufactured by Orient Chemical Industries, Ltd.), hexadecyltrimethylammonium bromide, "COPY CHARGE PX VP435" (manufactured by Clariant), etc.; polyamine resins, such as "AFP-B" (manufactured by Orient Chemical Industry Co., Ltd.), etc.; imidazole derivatives, such as "PLZ-2001" and "PLZ-8001" (manufactured by Shikoku Chemicals Co., Ltd.), etc.; styrene-acrylic resins, such as "FCA-701PT" (manufactured by Fujikura Chemicals Co., Ltd.).

[0205] In addition, negatively charged charge control agents include metal-containing azo dyes such as "VALIFAST Black 3804", "BONTRON S-31", "BONTRON S-32", "BONTRON S-34", "BONTRON S-36" (all manufactured by Orient Chemical Industry Co., Ltd.), "Aizen Spilon Black TRH", "T-77" (all manufactured by Hodogaya Chemical Industry Co., Ltd.), etc.; metal compounds of benzilic acid compounds such as "LR-147", "LR-297" (all manufactured by Nippon Carlit Co., Ltd.), etc.; metal compounds of salicylic acid compounds such as "BONTRON E-81", "BONTRON E-84", "BONTRON E-88", "BONTRON E-304" (all manufactured by Orient Chemical Industry Co., Ltd.), "TN-105" (all manufactured by Hodogaya Chemical Industry Co., Ltd.); copper phthalocyanine dyes; quaternary ammonium salts such as "COPY CHARGE NX VP434" (manufactured by Clariant), nitroimidazole derivatives, etc.; organic metal compounds, etc.

[0206] The content of the charge control agent is preferably 0.01 parts by mass or more, more preferably 0.2 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and further preferably 2 parts by mass or less, based on 100 parts by mass of the total amount of the resin components of the toner.

[0207] The volume median particle size (D50 ) is preferably 3 μm or more, more preferably 4 μm or more, further preferably 6 μm or more, and is preferably 15 μm or less, more preferably 10 μm or less.

[0208] It should be noted that in this specification, the volume median particle size (D 50 ) refers to the particle size at which the cumulative volume frequency calculated as a volume fraction reaches 50% when calculated from the smaller particle size side.

[0209] The content of the toner particles in the toner is preferably 90% by mass or more, more preferably 93% by mass or more, and further preferably 95% by mass or more, and is 100% by mass or less, and preferably 99% by mass or less.

[0210] <External additives>

[0211] In order to improve fluidity, it is preferred to use an external additive in the toner. Examples of the external additive include inorganic particles such as silicon dioxide particles, aluminum oxide particles, titanium dioxide particles, zirconium oxide particles, tin oxide particles, zinc oxide particles, and organic particles such as melamine resin particles and polytetrafluoroethylene resin particles. One or more of these can be used.

[0212] Examples of silica include hydrophobic silica subjected to a hydrophobic treatment.

[0213] Examples of the hydrophobizing agent for hydrophobizing the surface of the silica fine particles include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), silicone oil, octyltriethoxysilane (OTES), and methyltriethoxysilane. These can be used alone or in combination.

[0214] The number average particle size of the external additive is preferably 10 nm or more, more preferably 15 nm or more, and is preferably 200 nm or less, more preferably 120 nm or less, and further preferably 90 nm or less.

[0215] The content of the external additive is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and further preferably 0.3 parts by mass or more, and is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less, based on 100 parts by mass of the toner particles.

[0216] [Method for producing toner]

[0217] The colorant may be a colorant obtained by any known method such as melt kneading, emulsification phase inversion, polymerization, coagulation fusion, etc. From the viewpoint of productivity and dispersibility of the colorant, a pulverized colorant based on the melt kneading method or a chemical colorant based on the coagulation fusion method is preferred.

[0218] In the case of a pulverized colorant based on a melt-kneading method, for example, raw materials such as a binder resin, a colorant, a release agent, and a charge control agent are uniformly mixed using a mixer such as a Henschel mixer, and then melt-kneaded using a closed kneader, a single-screw or twin-screw extruder, an open roll-type mixer, etc., followed by cooling, pulverization, and classification to produce the colorant.

[0219] In the case of a chemical toner based on the aggregation and fusion method, it is preferred to have a step of agglomerating resin particles and, if necessary, colorant particles, release agent particles, etc. in an aqueous medium (step 1) and a step of fusing the agglomerated particles (step 2). In addition, step 1 is preferably a step of preparing a resin particle dispersion and, if necessary, a colorant particle dispersion, a release agent particle dispersion, etc., mixing them, and agglomerating the resin particles, colorant particles, release agent particles, etc.

[0220] <Process 1>

[0221] [Resin particle dispersion]

[0222] The resin particle dispersion contains resin particles X, and the resin particles X preferably contain amorphous polyester resin A and crystalline polyester resin C in the same or different particles, and further contain amorphous polyester resin B. In step 1, it is preferred to use resin particles containing resin A and resin C in the same particle, and it is more preferred to use resin particles containing resin A, resin B and resin C in the same particle.

[0223] The resin particle dispersion can be obtained by dispersing the resin in an aqueous medium.

[0224] As the aqueous medium, water is preferably used as the main component. From the viewpoint of improving the dispersion stability of the resin particle dispersion and reducing the environmental load, the content of water in the aqueous medium is preferably 80% by mass or more, more preferably 90% by mass or more, and further, 100% by mass or less. As components other than water that can be contained in the aqueous medium, organic solvents that are soluble in water can be cited.

[0225] Dispersion can be performed using a known method, and examples thereof include a method of adding an aqueous medium to an organic solvent solution of the resin or a molten resin to perform phase inversion emulsification.

[0226] The organic solvent used for phase inversion emulsification is not particularly limited as long as it dissolves the resin, but methyl ethyl ketone and ethyl acetate are preferred from the viewpoint of being easily removed from the mixed solution after the addition of the aqueous medium.

[0227] A neutralizing agent is added to the organic solvent solution as needed. Examples of the neutralizing agent include hydroxides of alkali metals such as sodium hydroxide and potassium hydroxide; and nitrogen-containing alkaline substances such as ammonia, trimethylamine, and diethanolamine.

[0228] The organic solvent solution or the molten resin is stirred while the aqueous medium is added to perform phase inversion. The stirring can be performed using a commonly used mixing and stirring device such as an anchor blade, a high-speed stirring and mixing device such as DISPER (manufactured by Asada Iron Works Co., Ltd.), TKHOMOMIXER, TKHOMODISPER, TKROBOMIX (all manufactured by PRIMIX Co., Ltd.), CLEARMIX (manufactured by M-Technique Co., Ltd.), and KD MILL (manufactured by KD International Co., Ltd.).

[0229] The temperature of the organic solvent solution when adding the aqueous medium varies depending on the boiling point of the organic solvent used, but is preferably above the glass transition temperature of the resin A constituting the resin particles X from the viewpoint of improving the dispersion stability of the resin particles X, and is preferably below 90°C, and more preferably below 80°C.

[0230] After the phase inversion emulsification, the organic solvent may be removed from the obtained dispersion by distillation or the like as necessary.

[0231] From the viewpoint of obtaining a toner capable of obtaining a high-quality image, the volume median particle size D of the resin particles X in the dispersion is 50 It is preferably 0.05 μm or more, more preferably 0.08 μm or more, and is preferably 1 μm or less, more preferably 0.5 μm or less, and further preferably 0.3 μm or less.

[0232] From the viewpoint of obtaining a toner capable of obtaining high-quality images, the CV value of the resin particles X in the dispersion is preferably 10% or more, more preferably 20% or more, and is preferably 40% or less, more preferably 35% or less.

[0233] Volume median particle size D 50 The CV value was determined by the method described in Examples below.

[0234] It should be noted that, when using a dispersion of resin particles containing resin A, a dispersion of resin particles containing resin C, and a dispersion of resin particles containing resin B, or when using a dispersion of resin particles containing resin A and resin C, and a dispersion of resin particles containing resin B, the above-mentioned method for producing resin particles X can be used for production. The volume median particle size D of the resin particles in the dispersion of these resin particles is 50 The preferred ranges of CV values ​​are the same as those described above.

[0235] Alternatively, the resin particle dispersion may be prepared by mixing the dispersion with a surfactant without using an organic solvent.

[0236] [Release agent particle dispersion]

[0237] The release agent particle dispersion is obtained by dispersing the release agent in an aqueous medium, preferably by dispersing the release agent at a temperature equal to or higher than the melting point of the release agent using a disperser. Examples of the disperser include a homogenizer and an ultrasonic disperser.

[0238] A preferred embodiment of the aqueous medium used in the release agent particle dispersion is the same as that used when obtaining the resin particle dispersion.

[0239] The dispersion of the release agent particles can also be obtained by using a surfactant, but is preferably obtained by mixing the release agent with the resin particles Z. The resin constituting the resin particles Z in which the release agent is dispersed is preferably a polyester resin. The preferred range of resin properties, the preferred production method, the particle size, the preferred range of CV value, etc. are the same as those of the above-mentioned resin particles X.

[0240] From the viewpoint of dispersion stability, the amount of the resin particles Z used is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, further preferably 20 parts by mass or more, and is preferably 70 parts by mass or less, more preferably 60 parts by mass or less, relative to 100 parts by mass of the release agent.

[0241] From the viewpoint of further improving the fixability to the PP film, the volume median particle size (D 50 ) is preferably 0.1 μm or more, more preferably 0.3 μm or more, and is preferably 1 μm or less, more preferably 0.7 μm or less.

[0242] From the viewpoint of dispersion stability of the release agent particles, the CV value of the release agent particles in the release agent particle dispersion is preferably 10% or more, more preferably 20% or more, and is preferably 40% or less, more preferably 30% or less.

[0243] [Colorant particle dispersion]

[0244] The colorant is preferably added in the form of a colorant particle dispersion containing colorant particles.

[0245] The colorant is preferably dispersed using a dispersant, preferably an anionic surfactant.

[0246] As the anionic surfactant, alkylbenzene sulfonates and alkyl ether sulfates are preferred.

[0247] From the viewpoint of obtaining a high-quality image, the volume median particle size (D 50) is preferably 0.05 μm or more, more preferably 0.08 μm or more, further preferably 0.1 μm or more, and is preferably 0.5 μm or less, more preferably 0.3 μm or less, further preferably 0.2 μm or less.

[0248] When other components such as a charge control agent are added, they are preferably added in the form of an aqueous dispersion similar to the release agent particle dispersion and the colorant particle dispersion.

[0249] In order to efficiently perform aggregation, it is preferred to add a coagulant in step 1.

[0250] [Coagulant]

[0251] Examples of the coagulant include cationic surfactants such as quaternary salts, organic coagulants such as polyethyleneimine, and inorganic coagulants. Examples of the inorganic coagulant include inorganic metal salts such as sodium sulfate, sodium nitrate, sodium chloride, calcium chloride, and calcium nitrate; inorganic ammonium salts such as ammonium sulfate, ammonium chloride, and ammonium nitrate; and metal complexes having a valence of two or more.

[0252] A coagulant is used, for example, by adding 5 parts by mass or more and 50 parts by mass or less of a coagulant relative to 100 parts by mass of the total amount of the resin to a mixed dispersion containing resin particles and colorant particles at a temperature of 0° C. or more and 40° C. or less, so that the resin particles and the colorant particles are coagulated in an aqueous medium to obtain coagulated particles. In addition, from the viewpoint of promoting coagulation, it is preferred to increase the temperature of the dispersion after adding the coagulant.

[0253] Resin particles containing resin A' may be further added to aggregated particles obtained by agglomerating resin particles containing at least resin A and resin C and, if necessary, release agent particles and colorant particles, to obtain aggregated particles in which resin particles containing resin A' are attached to aggregated particles containing resin particles containing resin A and resin C. In this way, toner particles having a core-shell structure containing resin particles containing resin A and resin C in the core portion and containing resin A' in the shell portion can be obtained.

[0254] The resin A' is preferably a polyester resin which is a polycondensate of an alcohol component and a carboxylic acid component. The resin A' is preferably an amorphous polyester resin.

[0255] Preferred examples of the alcohol component and carboxylic acid component of resin A' and preferred ranges of their physical properties are the same as those shown in the examples of the constituent parts derived from the polyester resin of amorphous polyester resin A. The method for obtaining a dispersion of resin particles containing resin A' is the same as the method for producing resin particles X.

[0256] The mass ratio of resin particles containing resin A' to resin particles containing resin A and resin C [A' / A+C] is preferably 0.05 or more, more preferably 0.1 or more, further preferably 0.13 or more, further preferably 0.15 or more, and is preferably 0.5 or less, more preferably 0.3 or less, further preferably 0.25 or less.

[0257] Aggregation can be stopped when the aggregated particles grow to a particle size suitable for toner particles.

[0258] Examples of the method for stopping aggregation include cooling the dispersion, adding an aggregation-stopping agent, and diluting the dispersion. From the viewpoint of reliably preventing unnecessary aggregation, the method of stopping aggregation by adding an aggregation-stopping agent is preferred.

[0259] [Agglomeration stopper]

[0260] As the aggregation-stopping agent, a surfactant is preferred, and an anionic surfactant is more preferred. The aggregation-stopping agent can be added in the form of an aqueous solution.

[0261] From the viewpoint of reliably preventing unnecessary aggregation, the amount of the aggregation-stopping agent added is preferably 1 part by mass or more, more preferably 5 parts by mass or more, relative to 100 parts by mass of the resin in the resin particles. Furthermore, from the viewpoint of reducing the residue in the colorant, it is preferably 60 parts by mass or less, more preferably 30 parts by mass or less, and further preferably 20 parts by mass or less.

[0262] The volume median particle size D of the agglomerated particles 50 It is preferably 2 μm or more, more preferably 3 μm or more, and even more preferably 4 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 6 μm or less. The volume median particle size D of the aggregated particles 50 It was determined by the method described in the Examples described later.

[0263] <Process 2>

[0264] In step 2, for example, aggregated particles are fused in an aqueous medium.

[0265] By fusion, the particles contained in the agglomerated particles are fused to obtain fused particles.

[0266] From the viewpoint of obtaining a high image density and a colorant in which a decrease in chargeability after storage under high temperature and high humidity is suppressed, the fusion temperature (hereinafter also referred to as "fusion temperature") is preferably a temperature that is 6°C lower than the melting point of resin C, more preferably a temperature that is 4°C lower, and further preferably a temperature that is 2°C lower. In addition, it is preferably a temperature that is 60°C higher or lower, more preferably a temperature that is 40°C higher or lower, and further preferably a temperature that is 20°C higher or lower.

[0267] The time for holding at the fusion temperature is not particularly limited, and the fusion can be terminated when the circularity of the fused particles is monitored and reaches an appropriate range.

[0268] In step 2, an acidic substance may be added to carry out fusion.

[0269] Examples of the acidic substance include inorganic acids and organic acids.

[0270] Among them, inorganic acids are preferred, and sulfuric acid is more preferred.

[0271] The method of adding the acidic substance may be a method of adding all at once, a method of adding the entire amount by dividing it into two or more times, or a method of adding it continuously for a certain period of time. From the viewpoint of suppressing further aggregation of the agglomerated particles, the method of adding by dividing it or the method of adding it continuously for a certain period of time is preferred. The temperature when adding the acidic substance is preferably within the range of the above-mentioned fusion temperature.

[0272] The volume median particle size D of the fused particles obtained by fusion 50 It is preferably 2 μm or more, more preferably 3 μm or more, and even more preferably 4 μm or more. It is also preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 6 μm or less. 50 The measurement is performed by the same method as that for toner particles described later.

[0273] The circularity of the fused particles obtained by fusion is preferably 0.955 or more, more preferably 0.960 or more, and is preferably 0.990 or less, more preferably 0.985 or less, and further preferably 0.980 or less.

[0274] <Post-processing process>

[0275] After step 2, a post-treatment step may be performed, and the fused particles may be separated by appropriately subjecting the particles to a solid-liquid separation step such as filtration, a washing step, and a drying step, thereby obtaining toner particles.

[0276] Toner is obtained by externally adding an external additive to the toner particles obtained in this way as required.

[0277] The toner may be used as a single-component developing toner or may be mixed with a carrier to be used as a two-component developer.

[0278] The toner is excellent in fixability to the PP film and scratch resistance to the PP film after printing, and therefore is preferably used as a toner for electrostatic charge development for printing on polypropylene films.

[0279] [Printing on PP film]

[0280] Printing on the PP film using toner can be performed using a common electrophotographic method.

[0281] Examples of PP films include untreated biaxially stretched PP films, corona-treated PP films, chemically treated PP films, plasma-treated PP films, and stretched films of composite resins of PP and other resins or additives. Untreated biaxially stretched PP films and corona-treated PP films are preferred from the perspective of cost.

[0282] The fixing temperature of the toner is preferably set to a temperature equal to or higher than the melting point of the polymer A from the viewpoint of effectively causing the interaction between the polymer A and the PP film.

[0283] The fixing temperature in the electrophotographic method is preferably 180° C. or lower, more preferably 160° C. or lower, and further preferably 140° C. or lower from the viewpoint of heat resistance of the PP film, and is preferably 70° C. or higher, more preferably 80° C. or higher, and further preferably 90° C. or higher from the viewpoint of fixability.

[0284] The present invention further discloses the following <1> to <46>.

[0285] <1> A toner for electrostatic image development, comprising a non-crystalline polyester resin A and a crystalline polyester resin C, wherein the non-crystalline polyester resin A has a constituent part derived from a polyester resin and a constituent part derived from a modified polyolefin polymer A having a reactive functional group, the constituent part derived from the polyester resin and the constituent part derived from the modified polyolefin polymer A are linked by a covalent bond, and the amount of the constituent part derived from the modified polyolefin polymer A is 5% by mass or more and 30% by mass or less relative to the total amount of resin components in the toner.

[0286] <2> The electrostatic image developing toner according to <1>, wherein the crystalline polyester resin C preferably has a solubility parameter based on Fedos of 9.0 (cal / cm 3 ) 1 / 2 More preferably, 9.2 (cal / cm 3 ) 1 / 2 More preferably, 9.4 (cal / cm3 ) 1 / 2 More than 10.5 (cal / cm 3 ) 1 / 2 Below, more preferably 10.3 (cal / cm 3 ) 1 / 2 Below, more preferably 9.9 (cal / cm 3 ) 1 / 2 Below, more preferably 9.8 (cal / cm 3 ) 1 / 2 Below, more preferably 9.7 (cal / cm 3 ) 1 / 2 Below, more preferably 9.6 (cal / cm 3 ) 1 / 2 the following.

[0287] <3> The electrostatic image developing toner according to <1> or <2>, wherein the crystalline polyester resin C has at least a polyester resin segment formed from a polycondensate of an alcohol component including an α,ω-aliphatic diol and a carboxylic acid component including an aliphatic dicarboxylic acid.

[0288] <4> In the electrostatic image developing toner according to <3>, the α,ω-aliphatic diol is preferably selected from ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol and 1,14-tetradecanediol, more preferably selected from ethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,10-decanediol and 1,12-dodecanediol, and further preferably selected from 1,10-decanediol and 1,12-dodecanediol.

[0289] <5> In the electrostatic image developing toner according to <3> or <4>, the content of α,ω-aliphatic diol in the alcohol component is preferably 80 mol% or more, more preferably 85 mol% or more, further preferably 90 mol% or more, further preferably 95 mol% or more, and is 100 mol% or less, further preferably 100 mol%.

[0290] <6> The electrostatic image developing toner according to any one of <3> to <5>, wherein the aliphatic dicarboxylic acid is preferably at least one selected from fumaric acid, sebacic acid, dodecanedioic acid and tetradecanedioic acid, more preferably at least one selected from sebacic acid and dodecanedioic acid, and even more preferably sebacic acid.

[0291] <7> In the electrostatic image developing colorant according to any one of <3> to <6>, the content of the aliphatic dicarboxylic acid in the carboxylic acid component is preferably 80 mol% or more, more preferably 85 mol% or more, further preferably 90 mol% or more, further preferably 95 mol% or more, and is 100 mol% or less, further preferably 100 mol%.

[0292] <8> In the electrostatic image developing toner according to any one of <3> to <7>, the amount of the polyester resin segment in the crystalline polyester resin C is preferably 40% by mass or more, more preferably 50% by mass or more, and is preferably 95% by mass or less, more preferably 85% by mass or less.

[0293] <9> The electrostatic image developing toner according to any one of <3> to <8>, wherein the crystalline polyester resin C further comprises an addition polymerization resin segment, wherein the addition polymerization resin segment is an addition polymer of a raw material monomer containing a styrene compound.

[0294] <10> In the electrostatic image developing toner according to <9>, the styrene compound is preferably at least one selected from styrene, methylstyrene, α-methylstyrene, β-methylstyrene, tert-butylstyrene, chlorostyrene, chloromethylstyrene, methoxystyrene, styrenesulfonic acid and salts thereof, and more preferably styrene.

[0295] <11> In the colorant for electrostatic image development according to <9> or <10>, the content of styrene-based compounds in the raw material monomers of the addition polymerization-based resin chain segment is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 90% by mass or more, and is less than 100% by mass, preferably less than 98% by mass, and more preferably less than 95% by mass.

[0296] <12> In the electrostatic image developing colorant according to any one of <9> to <11>, the amount of the addition polymerization resin chain segment in the crystalline polyester resin C is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, and is preferably 60% by mass or less, more preferably 50% by mass or less.

[0297] <13> The electrostatic image developing toner according to any one of <9> to <11>, wherein the crystalline polyester resin C has a structural unit derived from a bireactive monomer bonded to a polyester resin segment and an addition polymerization resin segment via a covalent bond.

[0298] <14> In the electrostatic image developing toner according to <13>, the bireactive monomer is preferably at least one selected from acrylic acid, methacrylic acid, fumaric acid, and maleic acid, more preferably at least one selected from acrylic acid and methacrylic acid, and even more preferably acrylic acid.

[0299] <15> In the electrostatic image developing colorant according to <13> or <14>, the content of the structural unit derived from the amphiphilic monomer in the crystalline polyester resin C is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and further preferably 0.8% by mass or more, and is preferably 10% by mass or less, more preferably 5% by mass or less, and further preferably 3% by mass or less.

[0300] <16> According to the colorant for electrostatic image development described in any one of <9> to <15>, the above-mentioned crystalline polyester resin C has a polyester resin segment and an addition polymerization resin segment, and the total amount of the polyester resin segment, the addition polymerization resin segment and the structural unit derived from the two reactive monomers is preferably 80 mass% or more, more preferably 90 mass% or more, further preferably 93 mass% or more, further preferably 95 mass% or more, and in addition, it is 100 mass% or less.

[0301] <17> In the electrostatic image developing colorant according to any one of <1> to <16>, the softening point of the crystalline polyester resin C is preferably 60°C or higher, more preferably 70°C or higher, further preferably 80°C or higher, and is preferably 170°C or lower, more preferably 150°C or lower, further preferably 120°C or lower, further preferably 110°C or lower.

[0302] <18> In the electrostatic image developing colorant according to any one of <1> to <17>, the melting point of the crystalline polyester resin C is preferably 50°C or higher, more preferably 60°C or higher, further preferably 70°C or higher, and is preferably 100°C or lower, more preferably 95°C or lower, further preferably 90°C or lower.

[0303] <19> In the electrostatic image developing colorant according to any one of <1> to <18>, the content of the crystalline polyester resin C relative to the total amount of all resin components in the colorant is preferably 0.1% by mass or more, more preferably 1% by mass or more, further preferably 3% by mass or more, and is preferably 60% by mass or less, more preferably 40% by mass or less, further preferably 35% by mass or less, further preferably 30% by mass or less, further preferably 20% by mass or less, further preferably 10% by mass or less.

[0304] <20> The electrostatic image developing toner according to any one of <1> to <19>, wherein the constituent part derived from the polyester resin and the constituent part derived from the modified polyolefin polymer A are linked via an ester bond.

[0305] <21> The electrostatic image developing toner according to any one of <1> to <20>, wherein the modified polyolefin polymer A is a modified polypropylene polymer.

[0306] <22> The electrostatic image developing toner according to any one of <1> to <21>, wherein the reactive functional group is a carboxylic acid group or a carboxylic anhydride group.

[0307] <23> According to the colorant for electrostatic image development described in any one of <1> to <22>, the modified polyolefin polymer A is a polypropylene polymer that has been terminally modified using a carboxylic acid compound having an unsaturated bond or its anhydride (terminal-modified polypropylene polymer), or a polypropylene polymer that has been randomly graft-modified using a carboxylic acid compound having an unsaturated bond or its anhydride (randomly graft-modified polypropylene polymer).

[0308] <24> The electrostatic image developing toner according to any one of <1> to <23>, wherein the modified polyolefin polymer A is a polypropylene polymer terminally modified with a carboxylic acid compound having an unsaturated bond or an anhydride thereof (terminally modified polypropylene polymer).

[0309] <25> The electrostatic image developing toner according to any one of <1> to <24>, wherein the modified polyolefin polymer A is a polypropylene polymer modified at only one end with a carboxylic acid compound having an unsaturated bond or an anhydride thereof (single-end modified polypropylene polymer).

[0310] <26> The electrostatic image developing colorant according to any one of <1> to <25>, wherein the modified polyolefin polymer A is preferably terminal maleic anhydride-modified polypropylene or a copolymer of terminal maleic anhydride-modified propylene and other olefins, more preferably terminal maleic anhydride-modified polypropylene, and even more preferably single-terminal maleic anhydride-modified polypropylene.

[0311] <27> According to the colorant for electrostatic image development according to any one of <1> to <26>, the melting point of the modified polyolefin polymer A is preferably 10°C or higher, more preferably 20°C or higher, further preferably 40°C or higher, further preferably 60°C or higher, further preferably 70°C or higher, further preferably 80°C or higher, and is preferably 170°C or lower, more preferably 150°C or lower, further preferably 140°C or lower, further preferably 120°C or lower, further preferably 100°C or lower.

[0312] <28> In the electrostatic image developing colorant according to any one of <1> to <27>, the acid value of the modified polyolefin polymer A is preferably 200 mgKOH / g or less, more preferably 150 mgKOH / g or less, further preferably 100 mgKOH / g or less, and is preferably 0.1 mgKOH / g or more, more preferably 1 mgKOH / g or more, further preferably 5 mgKOH / g or more, further preferably 10 mgKOH / g or more.

[0313] <29> In the electrostatic image developing colorant described in any one of <1> to <28>, the number average molecular weight of the modified polyolefin polymer A is preferably 300 or more, more preferably 500 or more, further preferably 700 or more, further preferably 800 or more, and is preferably 50,000 or less, more preferably 15,000 or less, further preferably 8,000 or less, further preferably 4,000 or less, further preferably 3,000 or less.

[0314] <30> In the colorant for electrostatic image development according to any one of <1> to <29>, the amount of constituent parts derived from the modified polyolefin polymer A in the above-mentioned amorphous polyester resin A is preferably 5% by mass or more, more preferably 8% by mass or more, further preferably 10% by mass or more, further preferably 15% by mass or more, and is preferably 80% by mass or less, more preferably 60% by mass or less, further preferably 40% by mass or less, and further preferably 35% by mass or less.

[0315] <31> The electrostatic image developing toner according to any one of <1> to <30>, wherein the amorphous polyester resin A is obtained by any one of the following methods (a) and (b).

[0316] (a) A method comprising polycondensing raw material monomers containing an alcohol component and a carboxylic acid component in the presence of a modified polyolefin polymer A having a reactive functional group.

[0317] (b) A method comprising reacting a modified polyolefin polymer A having a reactive functional group with a polyester resin

[0318] <32> In the electrostatic image developing colorant according to any one of <1> to <31>, the softening point of the amorphous polyester resin A is preferably 80°C or higher, more preferably 90°C or higher, further preferably 100°C or higher, preferably 170°C or lower, more preferably 150°C or lower, further preferably 120°C or lower, further preferably 110°C or lower.

[0319] <33> In the electrostatic image developing toner according to any one of <1> to <32>, the glass transition temperature of the amorphous polyester resin A is preferably 40°C or higher, more preferably 50°C or higher, and is preferably 80°C or lower, more preferably 70°C or lower, and further preferably 60°C or lower.

[0320] <34> According to any one of <1> to <33>, the crystalline melting peak of the above-mentioned non-crystalline polyester resin A originating from the constituent part of the modified polyolefin polymer A is preferably not observed or is below 140°C, more preferably below 130°C, further preferably below 120°C, further preferably below 110°C, and in addition, is preferably above 60°C, more preferably above 70°C, and further preferably above 80°C.

[0321] <35> According to any one of <1> to <34>, the content of the above-mentioned non-crystalline polyester resin A in the colorant for electrostatic image development is preferably 20% by mass or more, more preferably 30% by mass or more, and further preferably 40% by mass or more, relative to the total amount of resin components in the colorant. In addition, it is preferably 90% by mass or less, more preferably 80% by mass or less, further preferably 70% by mass or less, and further preferably 60% by mass or less.

[0322] <36> The electrostatic image developing toner according to any one of <1> to <35>, further comprising a non-crystalline polyester resin B having a softening point different from that of the non-crystalline polyester resin A by 5° C. or more.

[0323] <37> According to the colorant for electrostatic image development described in <36>, the mass ratio of the crystalline polyester resin to the total amount of the amorphous polyester resin A and the amorphous polyester resin B (resin C / (resin A+resin B)) is preferably 0.1 / 99.9 or more, more preferably 1 / 99 or more, further preferably 3 / 97 or more, and is preferably 60 / 40 or less, more preferably 40 / 60 or less, further preferably 35 / 65 or less, and further preferably 30 / 70 or less.

[0324] <38> In the electrostatic image developing colorant according to any one of <1> to <37>, the mass ratio of the amount of the constituent parts derived from the modified polyolefin polymer A to the amount of the crystalline polyester resin C is preferably 10 / 90 or more, more preferably 20 / 80 or more, further preferably 30 / 70 or more, further preferably 40 / 60 or more, and preferably 90 / 10 or less, more preferably 80 / 20 or less, further preferably 75 / 25 or less.

[0325] <39> The electrostatic image developing toner according to any one of <1> to <38>, wherein the electrostatic image developing toner is a pulverized toner obtained by a melt kneading method or a chemical toner obtained by an aggregation fusion method.

[0326] <40> The electrostatic image developing toner according to any one of <1> to <39>, which is a toner for electrostatic image developing for printing on polypropylene films.

[0327] <41> A printing method comprising printing on a polypropylene film by an electrophotographic method using the electrostatic image developing toner according to any one of <1> to <40>.

[0328] <42> According to the printing method described in <41>, the above-mentioned polypropylene film is preferably selected from untreated biaxially stretched PP film, corona treated PP film, chemically treated PP film, plasma treated PP film, and stretched film of composite resin of PP and other resins and additives, and is more preferably selected from untreated biaxially stretched PP film and corona treated PP film.

[0329] <43> The printing method according to <41> or <42>, wherein a fixing temperature of the toner in the electrophotographic method is equal to or higher than the melting point of the modified polyolefin polymer A.

[0330] <44> According to any one of <41> to <43>, the fixing temperature in the electrophotographic method is preferably 180°C or less, more preferably 160°C or less, further preferably 140°C or less, and preferably 70°C or more, more preferably 80°C or more, further preferably 90°C or more.

[0331] <45> A printed matter obtained by the method according to any one of <41> to <44>.

[0332] <46> A resin composition for a colorant for electrostatic image development, comprising a non-crystalline polyester resin A and a crystalline polyester resin C, wherein the non-crystalline polyester resin A has a constituent part derived from a polyester resin and a constituent part derived from a modified polyolefin polymer A having a reactive functional group, the constituent part derived from the polyester resin and the constituent part derived from the modified polyolefin polymer A are connected by a covalent bond, and the amount of the constituent part derived from the modified polyolefin polymer A is greater than 5% by mass and less than 30% by mass relative to the total amount of the resin components in the colorant.

[0333] Example

[0334] Each property was measured by the following method.

[0335] [Measurement method]

[0336] [Melting point of polymer A (Mp)]

[0337] The sample was heated to 200°C using a differential scanning calorimeter "DSC210" (manufactured by Seiko Instruments), and then cooled from this temperature to 0°C at a temperature drop rate of 10°C / min and then heated at a temperature rise rate of 10°C / min. The maximum peak temperature of the heat of fusion was defined as the melting point.

[0338] [Crystallization melting peak temperature of polymer A and polymer A monomer in resin]

[0339] For the sample of the resin or polymer A monomer, a differential scanning calorimeter "Q-20" (manufactured by TA Instruments Japan Co., Ltd.) was used to increase the temperature to 200°C at a heating rate of 10°C / min, and the maximum peak temperature of the endothermic absorption observed from the melting endothermic curve thus obtained was taken as the crystal melting peak temperature of polymer A. It should be noted that the crystal melting peak temperature of Ma-PP (Mn1000) in the table is 102°C.

[0340] [Acid value of resin and polymer A]

[0341] The measurement was performed according to the method of JIS K 0070: 1992. However, the measurement solvent was simply changed from the mixed solvent of ethanol and ether specified in JIS K 0070: 1992 to a mixed solvent of chloroform and dimethylformamide (hereinafter also referred to as "DMF") (chloroform:DMF=7:3 (volume ratio)).

[0342] [Softening point, maximum peak temperature, glass transition temperature and melting point of resin and polymer A]

[0343] (1) Softening point

[0344] Using a flow tester "CFT-500D" (manufactured by Shimadzu Corporation), 1 g of the sample was heated at a heating rate of 6°C / min, while a load of 1.96 MPa was applied through a plunger, and extruded from a nozzle with a diameter of 1 mm and a length of 1 mm. The plunger drop of the flow tester was plotted against the temperature, and the temperature at which half of the sample flowed out was taken as the softening point.

[0345] (2) The maximum peak temperature and melting point of the resin's endothermic properties

[0346] Using a differential scanning calorimeter "Q-20" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of the sample was measured in an aluminum pan, cooled from room temperature to 0°C at a cooling rate of 10°C / min, and allowed to stand for 1 minute in this state. Then, the measurement was performed at a heating rate of 50°C / min. Among the observed endothermic peaks originating from the resin or from the constituent parts of the polyester resin, the temperature of the peak appearing on the highest temperature side was taken as the maximum peak temperature of the endothermic heat of the resin. If the difference between the maximum peak temperature and the softening point is within 20°C, it is taken as the melting point.

[0347] The peak derived from the constituent part of the polyester resin can be assigned by a conventional method, but usually appears on the lower temperature side than the endothermic peak derived from the constituent part of the modified polyolefin-based polymer A. When it is unclear to which peak it should be assigned, the polyester resin alone and the modified polyolefin-based polymer A alone are measured under the above conditions using a differential scanning calorimeter, and the endothermic peak whose temperature is closer to each endothermic peak is assigned to the endothermic peak derived from each constituent part.

[0348] (3) Glass transition temperature

[0349] Using a differential scanning calorimeter "Q-20" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of a sample was weighed in an aluminum pan, heated to 200°C, and cooled from this temperature to 0°C at a temperature drop rate of 10°C / min. Next, the sample was heated at a temperature rise rate of 10°C / min and measured.

[0350] The temperature at the intersection of an extension line of the base line below the maximum peak temperature of the endothermic reaction and a tangent line showing a maximum slope from the rising portion of the peak to the peak apex was defined as the glass transition temperature.

[0351] [Melting point of release agent]

[0352] Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of a sample was weighed in an aluminum pan, heated to 200°C, and then cooled from 200°C to 0°C at a temperature drop rate of 10°C / min. Next, the sample was heated at a temperature rise rate of 10°C / min, the heat was measured, and the maximum peak temperature of the endothermic heat was taken as the melting point.

[0353] [Volume median particle size D of resin particles, release agent particles, and colorant particles 50 and CV value]

[0354] (1) Measurement device: Laser diffraction particle size measuring instrument "LA-920" (manufactured by Horiba, Ltd.)

[0355] (2) Measurement conditions: Distilled water was added to the measuring dish to make the absorbance reach the appropriate range, and the volume median particle size D was measured at this concentration. 50 The CV value (particle size distribution) was calculated according to the following formula.

[0356] CV value (%) = (standard deviation of particle size distribution / volume average particle size) × 100

[0357] [Solid Content Concentration of Resin Particle Dispersion Liquid, Release Agent Particle Dispersion Liquid, and Colorant Particle Dispersion Liquid]

[0358] The water content (mass %) of 5 g of the test sample was measured using an infrared moisture meter "FD-230" (manufactured by Kett Scientific Laboratory Co., Ltd.) at a drying temperature of 150°C and measurement mode 96 (monitoring time 2.5 min / variation range 0.05%). The solid content concentration was calculated according to the following formula.

[0359] Solid content (mass %) = 100 - water (mass %)

[0360] [Average particle size of external additives]

[0361] The average particle size of the external additive refers to the number average particle size, and the number average value of the particle size of 500 particles measured from a scanning electron microscope (SEM) photograph of the fluidizer and the external additive is taken as the average particle size of the fluidizer and the external additive. In the case of a major diameter and a minor diameter, the major diameter is used.

[0362] [Volume median diameter of toner particles (D 50 )]

[0363] The volume median particle size (D 50 ) was measured by the following method.

[0364] Measuring instrument: "Coulter Multisizer II" (manufactured by Beckman Coulter Co., Ltd.)

[0365] Pore ​​size: 100 μm

[0366] Analysis software: "Coulter Multisizer Accucomp Model 1.19" (manufactured by Beckman Coulter Co., Ltd.)

[0367] Electrolyte: "Isotone II" (manufactured by Beckman Coulter Co., Ltd.)

[0368] Dispersion liquid: "EMULGEN 109P" (manufactured by Kao Corporation, polyoxyethylene lauryl ether, HLB: 13.6) was dissolved in the above-mentioned electrolyte solution so as to have a concentration of 5% by mass.

[0369] Dispersion conditions: 10 mg of the measurement sample was added to 5 mL of the above dispersion, and dispersed with an ultrasonic disperser for 1 minute. Then, 25 mL of the above electrolyte was added, and dispersed with an ultrasonic disperser for further 1 minute to prepare a sample dispersion.

[0370] Measurement conditions: Add the sample dispersion to 100 mL of the electrolyte at a concentration that allows the measurement of 30,000 particles within 20 seconds, measure 30,000 particles, and calculate the volume median particle size (D 50 ).

[0371] [Manufacture of resin]

[0372] Production Examples A1 to A5, A81, B1 (Production of Resins A-1 to A-5, A-81, B-1)

[0373] The raw material monomers, esterification catalyst and co-catalyst of the polyester resin shown in Table 1 were added to a 10-liter four-necked flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser with a dehydration tube and a nitrogen inlet tube, and heated to 180°C in a nitrogen atmosphere, and then the temperature was raised by 5°C every hour to 230°C. After confirming that all the solid monomers were melted and reacted, the pressure was reduced to 8kPa, and dehydration condensation was carried out for 1 hour. Then, it was cooled to 160°C at normal pressure, polymer A was added, and after further reaction at 220°C for 1 hour, a condensation reaction was carried out under the conditions of 220°C and 8kPa, and the reaction was carried out until the softening point reached the softening point shown in Table 1, and resins A-1 to A-5, A-81, and B-1 were obtained. The physical properties of each resin were measured and shown in Table 1.

[0374] [Table 1-1]

[0375] Table 1(1 / 2)

[0376]

[0377] *1 indicates the number of moles when the total amount of the alcohol component is 100 moles.

[0378] *2 The amount of constituent parts derived from polymer A in the resin (mass %) is a value calculated by taking into account the amount of dehydration.

[0379] *3 Amount relative to 100 parts by mass of the raw material monomer of the polyester resin (parts by mass)

[0380] *4BPA-PO: Bisphenol A propylene oxide (2.2) adduct

[0381] BPA-EO: Bisphenol A ethylene oxide (2.2) adduct

[0382] *5Ma-PP (Mn1000): Single-end maleic anhydride-modified polypropylene "X-10065" (manufactured by Baker Hughes, number average molecular weight Mn1000, melting point 90°C, acid value 100 mgKOH / g)

[0383] *6Ma-PP / Hex (Mn4000): Single-end maleic anhydride-modified propylene / hexene copolymer "X-10052" (manufactured by BAKERHUGHES, number average molecular weight Mn4000, melting point 80°C, acid value 25 mgKOH / g)

[0384] *7PP / PE-g-Ma: Random graft maleic anhydride modified ethylene / propylene copolymer "TOYO-TAC PMA-T" (manufactured by Toyobo Co., Ltd., number average molecular weight Mn10600, melting point 93°C, acid value 35mKKOH / g)

[0385] [Table 1-2]

[0386] Table 1(2 / 2)

[0387]

[0388] *1 indicates the number of moles when the total amount of the alcohol component is 100 moles.

[0389] *2 The amount of constituent parts derived from polymer A in the resin (mass %) is a value calculated by taking into account the amount of dehydration.

[0390] *3 Amount relative to 100 parts by mass of the raw material monomer of the polyester resin (parts by mass)

[0391] *4BPA-PO: Bisphenol A propylene oxide (2.2) adduct

[0392] BPA-EO: Bisphenol A ethylene oxide (2.2) adduct

[0393] *5Ma-PP (Mn1000): Single-end maleic anhydride-modified polypropylene "X-10065" (manufactured by Baker Hughes, number average molecular weight Mn1000, melting point 90°C, acid value 100 mgKOH / g)

[0394] *6Ma-PP / Hex (Mn4000): Single-end maleic anhydride-modified propylene / hexene copolymer "X-10052" (manufactured by BAKERHUGHES, number average molecular weight Mn4000, melting point 80°C, acid value 25 mgKOH / g)

[0395] *7PP / PE-g-Ma: Random graft maleic anhydride modified ethylene / propylene copolymer "TOYO-TAC PMA-T" (manufactured by Toyobo Co., Ltd., number average molecular weight Mn10600, melting point 93°C, acid value 35 mgKOH / g)

[0396] Production Examples C1 to C6 (Resins C-1 to C-6)

[0397] The raw material monomers and esterification catalyst shown in Table 2 were added to a 10-liter four-necked flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, and heated from 130° C. to 200° C. over 10 hours under a nitrogen atmosphere, and reacted at 200° C. and 8 kPa for 1 hour to obtain resins C-1 to C-6. The physical properties of the obtained resins are shown in Table 2.

[0398] Production Examples C7, C8 (Resins C-7, C-8)

[0399] The raw material monomer (P) and esterification catalyst of the polyester resin shown in Table 2 are added to a 10L four-necked flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer and a thermocouple, heated to 160°C, and reacted for 6 hours. Then, using a dropping funnel, the raw material monomer (V), the two reactive monomers (D) and the polymerization initiator of the addition polymerization resin shown in Table 2 are added dropwise over 1 hour. After the addition polymerization reaction is matured at 160°C for 1 hour, it is maintained at 8.3 kPa for 1 hour. In addition, the temperature is raised to 200°C over 8 hours, and the reaction is carried out at 8.3 kPa for 2 hours to obtain resins C-7 and C-8. The physical properties of the obtained resins are shown in Table 2.

[0400] [Table 2-1]

[0401] Table 2 (1 / 2)

[0402]

[0403] *1 refers to the molar ratio of each monomer constituting the raw material monomer (P) and the bireactive monomer when the alcohol component of the raw material monomer (P) is 100 mol.

[0404] *2 refers to the amount (parts by mass) relative to 100 parts by mass of the raw material monomer (V).

[0405] *3 refers to the amount (parts by mass) relative to 100 parts by mass of the total amount of the raw material monomers (P).

[0406] *4 The polyester resin segment is the value obtained by removing the dehydration amount from the raw material monomer (P), and the addition polymerization segment includes the raw material monomer (V) and the polymerization initiator. (Mass ratio)

[0407] [Table 2-2]

[0408] Table 2 (2 / 2)

[0409]

[0410] *1 refers to the molar ratio of each monomer constituting the raw material monomer (P) and the bireactive monomer when the alcohol component of the raw material monomer (P) is 100 mol.

[0411] *2 refers to the amount (parts by mass) relative to 100 parts by mass of the raw material monomer (V).

[0412] *3 refers to the amount (parts by mass) relative to 100 parts by mass of the total amount of the raw material monomers (P).

[0413] *4 The polyester resin segment is the value obtained by removing the dehydration amount from the raw material monomer (P), and the addition polymerization segment includes the raw material monomer (V) and the polymerization initiator. (Mass ratio)

[0414] [Manufacturing of Resin Particle Dispersion]

[0415] Production Example X1 (Production of Resin Particle Dispersion Liquid X-1)

[0416] 300 g of resin A2, 270 g of resin B1, 30 g of resin C1, and 600 g of methyl ethyl ketone were added to a 3 L container equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, and dissolved at 73° C. for 2 hours. 107 g of a 5% by mass sodium hydroxide aqueous solution was added to the obtained solution, and stirred for 30 minutes.

[0417] Next, while maintaining the temperature at 73°C, 1200 g of deionized water was added over 1 hour while stirring at 200 r / min to perform phase inversion emulsification. Methyl ethyl ketone was distilled off from the obtained solution under reduced pressure to obtain an aqueous dispersion. Then, while continuing to stir, the aqueous dispersion was cooled to 30°C, and deionized water was added in a manner such that the solid content concentration became 35% by mass, thereby obtaining a resin particle dispersion X-1. The volume median particle size D50 of the obtained resin particles was 0.19 μm, and the CV value was 30%.

[0418] [Manufacturing of Release Agent Particle Dispersion]

[0419] Production Example W1 (Production of Release Agent Particle Dispersion Liquid W-1)

[0420] In a 1-liter beaker, add 130 g of deionized water, 45.7 g of resin particle dispersion X-1, and 40 g of paraffin "HNP-9" (manufactured by Nippon Seiki Co., Ltd., melting point 75°C), and stir to obtain a molten mixture. While maintaining the temperature at 90-95°C, use an ultrasonic homogenizer "US-600T" (manufactured by Nippon Seiki Co., Ltd.) to perform dispersion treatment for 20 minutes, and then cool to room temperature. Add deionized water and adjust the solid content concentration to 20% by mass to obtain a release agent particle dispersion W-1. The volume median particle size D of the release agent particles in the dispersion is 50 The thickness is 0.57 μm and the CV value is 27%.

[0421] [Manufacturing of Colorant Dispersion]

[0422] Production Example E1 (Production of Colorant Dispersion Liquid E-1)

[0423] In a 1-liter beaker, 67.5 g of copper phthalocyanine pigment "ECB-301" (CI Pigment Blue 15:3, manufactured by Dainichi Seika Industries, Ltd.), 189 g of anionic surfactant "NEOPELEX (registered trademark) G-15" (manufactured by Kao Corporation, 15% by mass aqueous solution of sodium dodecylbenzenesulfonate) and 100 g of deionized water were mixed and dispersed at room temperature for 3 hours using a homogenizer. Deionized water was then added so that the solid content concentration became 25% by mass, thereby obtaining a colorant dispersion E-1. Volume median particle size D of the colorant particles in the dispersion 50 It is 125nm.

[0424] [Manufacturing of toner]

[0425] Examples 1 to 13, 15, 16 and Comparative Examples 1 and 2 (Manufacturing of Toners 1 to 13, 15, 16, 81 and 82)

[0426] 100 parts by mass of the binder resin shown in Table 3, a release agent "HNP-9" (manufactured by Nippon Seika Co., Ltd., paraffin wax, melting point: 80°C), 0.5 parts by mass of a charge control agent "BONTRON E-304" (manufactured by Orient Chemical Industry Co., Ltd.), and 4.5 parts by mass of a colorant "ECB-301" (manufactured by Dainichi Seika Industries, Ltd., CI Pigment Blue 15:3) were fully mixed with a Henschel mixer and melt-kneaded under the conditions shown below.

[0427] A continuous double open roll type kneading mill "Kneedex" (manufactured by Mitsui Mining Co., Ltd., roll outer diameter: 14 cm, effective roll length: 80 cm) was used. The operating conditions of the continuous double open roll type kneading mill were set to a high rotation side roll (front roll) peripheral speed of 32.4 m / min, a low rotation side roll (rear roll) peripheral speed of 21.7 m / min, and a roll gap of 0.1 mm. The heating medium temperature and the cooling medium temperature in the roll were set to: 145°C for the raw material input side of the high rotation side roll and 100°C for the kneaded material discharge side, and 75°C for the raw material input side of the low rotation side roll and 35°C for the kneaded material discharge side. In addition, the supply rate of the raw material mixture was 10 kg / hr, and the average residence time was about 3 minutes.

[0428] The obtained resin mixture is cooled and coarsely pulverized using a pulverizer "Rotoplex" (manufactured by Hosokawamicron Co., Ltd.), and a coarse pulverized product having a volume median particle size of less than 2 mm is obtained using a sieve with a mesh size of 2 mm. The obtained coarse pulverized product is finely pulverized by adjusting the pulverizing pressure using an airflow classifier "DS2" (collision plate type, manufactured by Japan Pneumatic Co., Ltd.) so that the volume median particle size (D50) reaches 7.5 μm. The obtained finely pulverized product is classified by adjusting the static pressure (internal pressure) using an airflow classifier "DSX2" (manufactured by Japan Pneumatic Co., Ltd.) so that the volume median particle size (D 50 ) reached 8.5 μm, and toner particles were obtained.

[0429] To 100 parts by mass of the obtained colorant particles, 1.0 parts by mass of external additives "R972" (hydrophobic silica, manufactured by Nippon Aerosil Co., Ltd., number average particle size: 16 nm) and 1.0 parts by mass of "RX50" (hydrophobic silica, manufactured by Nippon Aerosil Co., Ltd., number average particle size: 40 nm) were added, and mixed at 3700 r / min for 3 minutes using a Henschel mixer to perform external additive treatment, thereby obtaining colorants 1 to 13, 15, 16, 81 and 82.

[0430] Example 14 (Manufacturing of Toner 14)

[0431] In Example 2, the toner raw materials were mixed with a Henschel mixer and then melt-kneaded under the following conditions.

[0432] A co-rotating twin-screw extruder with a total length of 1560 mm, a screw diameter of 42 mm, and a barrel inner diameter of 43 mm was used to perform melt kneading at a roll speed of 200 r / min and a heating temperature in the roll of 100° C. The feed rate of the mixture was 20 kg / h, and the average residence time was about 18 seconds.

[0433] The obtained resin kneaded product was coarsely pulverized, finely pulverized, and classified in the same manner as in Example 2 to obtain toner particles.

[0434] The obtained toner particles were mixed with an external additive in the same manner as in Example 2 to obtain Toner 14 .

[0435] Example 17 (Manufacturing of Toner 17)

[0436] In a 5 L four-necked flask equipped with a dehydration tube, a stirring device and a thermocouple, 500 g of the resin particle dispersion X-1, 37 g of the release agent particle dispersion W-1, 45 g of the colorant particle dispersion E-1, 18 g of a 10% by mass aqueous solution of polyoxyethylene (50) lauryl ether "EMULGEN 150" (manufactured by Kao Corporation, a nonionic surfactant), and 18 g of a 15% by mass aqueous solution of sodium dodecylbenzenesulfonate "NEOPELEX G-15" (manufactured by Kao Corporation, anionic surfactant) were mixed at 25° C. Next, while stirring the mixture, a solution obtained by adding 27 g of a 4.8% by mass aqueous solution of potassium hydroxide to an aqueous solution of 62 g of ammonium sulfate dissolved in 967 g of deionized water was added dropwise at 25° C. over 10 minutes, and the mixture was heated to 68° C. over 2 hours to obtain a dispersion of aggregated particles.

[0437] To the obtained dispersion of aggregated particles, an aqueous solution obtained by mixing 156 g of sodium polyoxyethylene lauryl ether sulfate "EMAL E-27C" (manufactured by Kao Corporation, an anionic surfactant, effective concentration 27 mass %), 958 g of deionized water, and 58 g of a 0.1 mol / L aqueous sulfuric acid solution was added. Then, the temperature was raised to 90° C. over 1 hour and maintained at 90° C. for 30 minutes, thereby obtaining a volume median particle size D 50 It is a dispersion of fused particles of 8.5 μm.

[0438] The obtained dispersion of fused particles was cooled to 30° C., and the solid content was separated by suction filtration. The solid content was then washed with deionized water at 25° C. and then vacuum dried at 30° C. for 48 hours to obtain toner particles.

[0439] To 100 parts by mass of the obtained colorant particles, 1.0 parts by mass of external additives “R972” (hydrophobic silica, manufactured by Nippon Aerosil Co., Ltd., number average particle size: 16 nm) and 1.0 parts by mass of “RX50” (hydrophobic silica, manufactured by Nippon Aerosil Co., Ltd., number average particle size: 40 nm) were added, and the mixture was mixed at 3700 r / min for 3 minutes using a Henschel mixer to perform external additive treatment to obtain colorant 17.

[0440] [Evaluation method]

[0441] [PP film fixability]

[0442] A non-magnetic single-component developing device "OKI MICROLINE 5400" (manufactured by Oki Data Co., Ltd.) was filled with toner, and the toner adhesion amount was adjusted to 0.45±0.03 mg / cm 2 A solid image of 2.0 cm×1.5 cm was printed on an untreated biaxially stretched polypropylene film “TREFAN Industrial Type 2500” (manufactured by Toray Industries, Ltd., thickness 60 μm), and fixed at a fixing temperature of 140°C.

[0443] The fixed image was peeled off with a transparent tape, and the fixing rate was calculated by [(image area before tape peeling - image area after tape peeling) / (image area before tape peeling)] × 100. The higher the fixing rate, the higher the fixing property of the PP film.

[0444] [T-peel strength]

[0445] A non-magnetic single-component developing device "OKI MICROLINE 5400" (manufactured by Oki Data Co., Ltd.) was filled with toner, and the toner adhesion amount was adjusted to 0.45±0.03 mg / cm 2 A solid image of 2.5 cm × 15.0 cm was printed on an untreated biaxially stretched polypropylene film "TREFAN Industrial Type 2500" (manufactured by Toray Industries, Ltd., thickness 60 μm). A new untreated biaxially stretched polypropylene film was covered on the printed image and fixed directly at a fixing temperature of 150°C. The prepared sample was peeled off at a moving speed of 100 mm / min using a table-top material testing machine (A&D Co., Ltd.), and the load applied at this time was measured.

[0446] [Scratch resistance]

[0447] A non-magnetic single-component developing device "OKI MICROLINE 5400" (manufactured by Oki Data Co., Ltd.) was filled with toner, and the toner adhesion amount was adjusted to 0.45±0.03 mg / cm 2 A solid image of 2.0 cm×1.5 cm was printed on an untreated biaxially stretched polypropylene film “TREFAN Industrial Type 2500” (manufactured by Toray Industries, Ltd., thickness 60 μm), and fixed at a fixing temperature of 140°C.

[0448] The fixed image was scratched using a friction fastness tester (Daiei Kagaku Seiki Mfg. Co., Ltd.) to evaluate the toner layer peeling. The load during the rubbing was 300 g, and the number of rubbings was 100 times, 300 times, and 500 times.

[0449] (Evaluation Criteria)

[0450] A: No peeling of the toner layer was observed at 500 rubbing times

[0451] B: No peeling of the toner layer was observed at 300 rubbing times, but peeling of the toner layer was observed at 500 rubbing times

[0452] C: No peeling of the toner layer was observed at 100 times of rubbing, but peeling of the toner layer was observed at 300 times of rubbing

[0453] D: Peeling of the toner layer was observed even at 100 times of friction

[0454] [Table 3]

[0455] Table 3

[0456]

[0457] *1 Amount of constituent parts derived from polymer A relative to the total amount of amorphous resin A, amorphous resin B and crystalline resin C (mass %)

[0458] As described above, it is understood that the toners of Examples show excellent fixability and scratch resistance to PP films compared to the toners of Comparative Examples.

Claims

1. A toner for electrostatic image development, characterized in that: Containing a non-crystalline polyester resin A and a crystalline polyester resin C, The amorphous polyester resin A has a constituent part derived from the polyester resin and a constituent part derived from the modified polyolefin polymer A having a reactive functional group, wherein the constituent part derived from the polyester resin and the constituent part derived from the modified polyolefin polymer A are connected by a covalent bond, The amount of the structural part derived from the modified polyolefin polymer A is 5% by mass or more and 15% by mass or less based on the total amount of the resin components in the toner.

2. The electrostatic image developing toner according to claim 1, wherein The solubility parameter of the crystalline polyester resin C based on Fedos is 9.0 (cal / cm 3 ) 1 / 2 Above and 10.5 (cal / cm 3 ) 1 / 2 the following.

3. The electrostatic image developing toner according to claim 1 or 2, wherein The crystalline polyester-based resin C has at least a polyester resin segment formed of a polycondensate of an alcohol component including an α,ω-aliphatic diol and a carboxylic acid component including an aliphatic dicarboxylic acid.

4. The electrostatic image developing toner according to claim 3, wherein The amount of the polyester resin segment in the crystalline polyester resin C is 40% by mass or more and 95% by mass or less.

5. The electrostatic image developing toner according to claim 3, wherein The crystalline polyester-based resin C further has an addition polymerization-based resin segment, and the addition polymerization-based resin segment is an addition polymer of a raw material monomer including a styrene-based compound.

6. The electrostatic image developing toner according to claim 5, wherein The amount of the addition polymerization-based resin segment in the crystalline polyester-based resin C is 5% by mass or more and 60% by mass or less.

7. The electrostatic image developing toner according to claim 5 or 6, wherein The crystalline polyester resin C has a structural unit derived from a bireactive monomer bonded to the polyester resin segment and the addition polymerization resin segment through a covalent bond.

8. The electrostatic image developing toner according to claim 5 or 6, wherein The crystalline polyester resin C has the polyester resin segment and the addition polymerization resin segment, and the total amount of the polyester resin segment, the addition polymerization resin segment, and the structural unit derived from the bireactive monomer is 80% by mass or more.

9. The electrostatic image developing toner according to claim 1 or 2, wherein The melting point of the crystalline polyester resin C is 50° C. or higher and 100° C. or lower.

10. The electrostatic image developing toner according to claim 1 or 2, wherein The constituent part derived from the polyester resin and the constituent part derived from the modified polyolefin polymer A are connected via an ester bond.

11. The electrostatic image developing toner according to claim 1 or 2, wherein The modified polyolefin polymer A is a modified polypropylene polymer.

12. The electrostatic image developing toner according to claim 1 or 2, wherein The reactive functional group is a carboxylic acid group or a carboxylic anhydride group.

13. The electrostatic image developing toner according to claim 1 or 2, wherein The number average molecular weight of the modified polyolefin polymer A is 500 or more and 8000 or less.

14. The electrostatic image developing toner according to claim 1 or 2, wherein The modified polyolefin polymer A is a polypropylene polymer terminally modified with a carboxylic acid compound having an unsaturated bond or an anhydride thereof.

15. The electrostatic image developing toner according to claim 1 or 2, wherein The modified polyolefin polymer A is a polypropylene polymer modified at only one end with a carboxylic acid compound having an unsaturated bond or an anhydride thereof.

16. The electrostatic image developing toner according to claim 1 or 2, wherein The modified polyolefin polymer A is terminal maleic anhydride-modified polypropylene or a copolymer of terminal maleic anhydride-modified propylene and other olefins.

17. The electrostatic image developing toner according to claim 1 or 2, wherein: The melting point of the modified polyolefin polymer A is 10° C. or higher and 170° C. or lower.

18. The electrostatic image developing toner according to claim 1 or 2, wherein The softening point of the amorphous polyester resin A is 80° C. or higher and 170° C. or lower.

19. The electrostatic image developing toner according to claim 1 or 2, wherein The content of the non-crystalline polyester resin A is 20% by mass or more and 90% by mass or less based on the total amount of the resin components in the toner.

20. The electrostatic image developing toner according to claim 1 or 2, wherein The present invention further contains a non-crystalline polyester resin B having a softening point different from that of the non-crystalline polyester resin A by 5° C. or more.

21. The electrostatic image developing toner according to claim 20, wherein The mass ratio of the crystalline polyester resin C to the total amount of the amorphous polyester resin A and the amorphous polyester resin B, that is, resin C / (resin A+resin B), is 0.1 / 99.9 or more and 60 / 40 or less.

22. The electrostatic image developing toner according to claim 1 or 2, wherein The content of the crystalline polyester resin C is 3% by mass or more and 40% by mass or less relative to the total amount of all resin components in the toner.

23. The electrostatic image developing toner according to claim 1 or 2, wherein The amount of the constituent part derived from the modified polyolefin polymer A in the amorphous polyester resin A is 5% by mass or more and 80% by mass or less.

24. The electrostatic image developing toner according to claim 1 or 2, wherein The mass ratio of the amount of the structural part derived from the modified polyolefin-based polymer A to the amount of the crystalline polyester-based resin C is 10 / 90 or more and 90 / 10 or less.

25. Use of the electrostatic image developing toner according to any one of claims 1 to 24 for printing on a polypropylene film.

26. A printing method, wherein: Printing is performed on a polypropylene film by an electrophotographic method using the electrostatic image developing toner according to any one of claims 1 to 24, wherein the fixing temperature of the toner is equal to or higher than the melting point of the modified polyolefin polymer A.

27. A printing method, characterized in that: Using the electrostatic image developing toner according to any one of claims 1 to 24, printing is performed on a polypropylene film at a fixing temperature of 70°C or higher and 180°C or lower by an electrophotographic method.

28. A printed matter obtained by the method according to any one of claims 26 to 27.

29. A resin composition for electrostatic image developing toner, characterized in that: Containing a non-crystalline polyester resin A and a crystalline polyester resin C, The amorphous polyester resin A has a constituent part derived from the polyester resin and a constituent part derived from the modified polyolefin polymer A having a reactive functional group, wherein the constituent part derived from the polyester resin and the constituent part derived from the modified polyolefin polymer A are connected by a covalent bond, The amount of the structural part derived from the modified polyolefin polymer A is 5% by mass or more and 15% by mass or less based on the total amount of the resin components in the toner.

Citation Information

Patent Citations

  • Compatibilizer, polyester resin composition for toner, and toner

    JP2005316378A

  • Electrostatic charge image developing toner and method for manufacturing the same

    JP2007199300A

  • Binder resin composition for electrostatic charge image developing toner

    JP2016218448A

  • Binder resin composition for electrostatic image developing toners

    EP3299892A1

  • Toner resin composition and toner

    JP2006098804A